Zirconia composition and method for producing same

By adjusting the composition of the zirconia composition, especially adding transition metal elements and lanthanide rare earth elements, the problems of uneven coloring and hardness differences in the zirconia sintered body are solved, and the uniform hardness and color consistency of the pre-sintered body are achieved.

CN119894846APending Publication Date: 2025-04-25TOSOH CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380067499.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-10
Filing Date
2023-09-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, when preparing zirconia sintered bodies, it is difficult to uniformly color and adjust the tone, and the hardness of the pre-sintered bodies is relatively different, which affects the processing difficulty.

Method used

By adjusting the composition of the zirconia composition, especially the addition of transition metal elements and lanthanide rare earth elements, controlling their heat shrinkage behavior, a preburned body with uniform tone and reduced hardness differences is prepared.

Benefits of technology

The uniform hardness and color consistency of the preburned body are achieved, which reduces the difficulty of processing and suppresses the hardness difference between manufacturing batches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005320496600000381
    Figure BDA0005320496600000381
  • Figure BDA0005320496600000431
    Figure BDA0005320496600000431
  • Figure BDA0005320496600000441
    Figure BDA0005320496600000441
Patent Text Reader

Abstract

Provided are at least one of a pre-sintered body, a method for producing the same, a sintered body obtained thereby, and a zirconia composition that is a starting material for such a pre-sintered body, said pre-sintered body being easier to process than conventional pre-sintered bodies and having suppressed differences in hardness between production batches. The present invention also provides a method for producing the pre-sintered body, a sintered body obtained thereby, and a zirconia composition that is a starting material for such a pre-sintered body. A zirconia composition containing a first transition metal element, a coloring element, and zirconia containing a stabilizing element, the first transition metal element being one or more elements selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), and silver (Ag), the coloring element being one or more elements selected from the group consisting of cobalt (Co), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), and silver (Ag); the coloring element is at least one of a lanthanide rare earth element and a second transition metal element different from the first transition metal element, the content of the first transition metal element is 100 ppm by mass or more, and the content of the second transition metal element is less than 100 ppm by mass. The ratio of measurement points at which the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of the zirconium element is 0.05 or more when the characteristic X-ray of the zirconium element and the characteristic X-ray of the first transition metal element are measured is 3% or less of all the measurement points; the distribution width of the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of the zirconium element is 0.3 or less when the characteristic X-ray of the zirconium element and the characteristic X-ray of the first transition metal element are measured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition containing zirconium oxide as a main component and a method for producing the same. Background Art

[0002] Sintered bodies of zirconium oxide (ZrO2; zirconium dioxide) containing coloring components are used in a wide range of applications such as mobile electronic device components, decorative components, and dental restorations. Sintered bodies of zirconium oxide have high strength and are difficult to process. Therefore, in the case of obtaining a sintered body with a complex shape such as a dental restoration, a so-called pre-sintered body (semi-sintered body, pre-sintered body) is used, which is obtained by heat treating a zirconium oxide molded body (powder compact) at a temperature lower than the sintering temperature and having a strength suitable for processing. The pre-sintered body is cut into the desired shape using CAD / CAM and then sintered to produce a sintered body.

[0003] In order to obtain a sintered body having the color tone of natural teeth, there is a method of sintering a calcined body of zirconium oxide immersed in a coloring solution (so-called immersion method) (for example, Patent Document 1). The calcined body colored by the immersion method has uneven coloring caused by the difference in the degree of penetration of the coloring solution between the surface and the inside of the calcined body. In addition, in the immersion method, it is difficult to obtain a fine color tone that matches the color tone of the natural teeth of each patient.

[0004] On the other hand, there is known a method of molding and pre-firing a powder composition obtained by mixing a coloring component and zirconium oxide in a powder state, and sintering the pre-firing body containing the coloring component at the time of pre-firing (so-called powder mixing method) (Patent Document 2). The pre-firing body obtained by the powder mixing method has extremely small color unevenness compared to the pre-firing body obtained by the impregnation method, and it is also easy to finely adjust the color tone of the obtained sintered body.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: European Patent Application Publication No. 3892254

[0008] Patent Document 2: U.S. Patent No. 9428422 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] The color tone of the sintered body obtained from the calcined body is determined by adjusting the composition, especially the type and content of the coloring component. On the other hand, even a trace amount of the coloring component will affect the thermal shrinkage behavior of the zirconium oxide composition. Therefore, the thermal shrinkage behavior of zirconium oxide compositions with different compositions is different from each other. As a result, the calcined bodies that provide sintered bodies with different color tones have different hardnesses. The calcined bodies with different hardnesses impose different burdens on the processing tools, so skilled processing technology is required. Furthermore, the higher the hardness, the more difficult it is to process the calcined body.

[0011] In addition to the difference in processing characteristics caused by the difference in composition, the hardness of the calcined body obtained by calcining the molded body containing the coloring component is sometimes different between the production batches, even if it is a calcined body of the same composition. By applying different calcining conditions according to the composition (color tone) of the calcined body, the hardness difference caused by the composition difference can be suppressed to some extent. However, changing the calcining conditions according to the composition of the calcined body makes the production process of the calcined body complicated, so it is not preferred. Furthermore, in the calcined body of the same composition, even if multiple calcining conditions are applied, the hardness difference between the production batches cannot be suppressed.

[0012] In view of the above circumstances, an object of the present invention is to provide at least any one of a calcined body, a method for producing the same, a sintered body obtained therefrom, and a zirconium oxide composition as a raw material of such a calcined body, wherein the calcined body is easier to process than conventional calcined bodies and has reduced hardness variation between production lots.

[0013] Technical solutions for solving technical problems

[0014] The inventors of the present invention have studied the thermal shrinkage behavior and composition of a zirconium oxide composition as a precursor of a calcined body in detail. As a result, it was found that even among coloring components, transition metal elements have a great influence on the thermal shrinkage behavior of the zirconium oxide composition, and that by controlling the state of the transition metal element above a certain content, the thermal shrinkage behavior can be changed without changing the essential composition. As a result, a calcined body having the same color tone as a sintered body obtained from a conventional calcined body and suppressing the hardness difference of the calcined body between production batches, and a zirconium oxide composition as a precursor of such a calcined body were found.

[0015] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows.

[0016] [1] A zirconium oxide composition comprising a first transition metal element, a coloring element, and zirconium oxide containing a stabilizing element,

[0017] The first transition metal element is one or more selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd) and silver (Ag),

[0018] The coloring element is at least one of a lanthanide rare earth element and a second transition metal element different in type from the first transition metal element.

[0019] The content of the first transition metal element is 100 mass ppm or more,

[0020] The content of the second transition metal element is less than 100 mass ppm, and

[0021] The zirconium oxide composition satisfies at least any one of the following characteristics:

[0022] When measuring the characteristic X-ray of zirconium and the characteristic X-ray of the first transition metal element, the proportion of measurement points at which the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of zirconium is 0.05 or more is less than 3% of all the measurement points; and

[0023] When the characteristic X-rays of zirconium and the characteristic X-rays of the first transition metal element are measured, the distribution width of the ratio of the intensity of the characteristic X-rays of the first transition metal element to the intensity of the characteristic X-rays of zirconium is less than 0.3.

[0024] [2] The zirconium oxide composition according to [1] above, wherein, when the characteristic X-rays of the zirconium element and the characteristic X-rays of the first transition metal element are measured, the distribution width of the ratio of the intensity of the characteristic X-rays of the first transition metal element to the intensity of the characteristic X-rays of the zirconium element is less than 0.3.

[0025] [3] The zirconium oxide composition according to [1] or [2] above, wherein, when measuring the characteristic X-ray of the zirconium element and the characteristic X-ray of the first transition metal element, the proportion of measurement points at which the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of the zirconium element is 0.05 or more is less than 3% of all the measurement points.

[0026] [4] The zirconium oxide composition according to any one of [1] to [3] above, wherein the second transition metal element is one or more transition metal elements selected from the group consisting of manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver.

[0027] [5] The zirconium oxide composition according to any one of [1] to [4] above, wherein the lanthanide rare earth element is one or more selected from praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), erbium (Er) and ytterbium (Yb).

[0028] [6] The zirconium oxide composition according to any one of [1] to [5] above, wherein the lanthanide rare earth element is a lanthanide rare earth element that is solid-dissolved in zirconium oxide.

[0029] [7] The zirconium oxide composition according to any one of [1] to [6] above, wherein the content of the lanthanide rare earth element is 1.0 mass % or less.

[0030] [8] The zirconium oxide composition according to any one of [1] to [7] above, wherein the zirconium oxide composition contains one or more third transition metal elements selected from titanium (Ti), vanadium (V) and niobium (Nb).

[0031] [9] The zirconium oxide composition according to any one of [1] to [8] above, wherein the zirconium oxide composition contains one or more selected from aluminum oxide (Al2O3), silicon dioxide (SiO2) and germanium oxide (Ge2O3).

[0032]

[10] The zirconium oxide composition according to any one of [1] to [9] above, wherein the BET specific surface area of ​​the zirconium oxide composition is 8 m 2 / g or more and 15m 2 / g or less.

[0033]

[11] The zirconium oxide composition according to any one of [1] to

[10] above, wherein the zirconium oxide composition is a powder.

[0034]

[12] The zirconium oxide composition according to

[11] , wherein 3.0±0.1 g of the zirconium oxide composition is filled into a mold with a diameter of 25 mm, subjected to uniaxial press molding at a pressure of 49 MPa, and subjected to CIP treatment at a pressure of 196 MPa, the measured density is 3.2 g / cm 3 above.

[0035]

[13] The zirconium oxide composition according to any one of [1] to

[10] above, wherein the zirconium oxide composition is a molded body.

[0036]

[14] The zirconium oxide composition according to

[13] above, wherein the Vickers hardness of the zirconium oxide composition is 11.0 or more.

[0037]

[15] A method for producing a calcined body, comprising the step of calcining the zirconium oxide composition according to any one of [1] to

[14] above.

[0038]

[16] A method for producing a sintered body, comprising the step of sintering the calcined body obtained by the production method according to

[15] above.

[0039] Effects of the Invention

[0040] According to the present invention, it is possible to provide at least any one of a calcined body that is easier to process than conventional calcined bodies and in which hardness variation between production lots is suppressed, a method for producing the same, a sintered body obtained therefrom, and a zirconium oxide composition as a raw material of the calcined body. DETAILED DESCRIPTION

[0041] The zirconium oxide composition of the present invention will be described below with reference to one embodiment. The terms used in this embodiment are as follows.

[0042] "Composition" refers to a substance having a certain composition, for example, one or more selected from powder, molded body, calcined body and sintered body. "Zirconium oxide composition" refers to a composition with zirconium oxide as the main component, and further refers to a composition essentially composed of zirconium oxide. It may also contain components other than zirconium oxide. Preferably, the zirconium oxide composition in this embodiment is a composition that can be a precursor of a calcined body.

[0043] "Powder" refers to an aggregate of powder particles (at least one of primary particles and secondary particles), and is a composition having fluidity. "Zirconium oxide powder" refers to a powder having zirconium oxide as the main component, and is a powder essentially composed of zirconium oxide. In addition, "powder composition" refers to a composition composed of powders with different characteristics, in particular, a composition containing powders with different compositions.

[0044] "Granular powder" refers to an aggregate of powder particles (granular particles), and is a fluid composition, especially a composition in which the powder particles are in a slowly agglomerated state. "Zirconium oxide granular powder" refers to a granular powder with zirconium oxide as the main component, and is a granular powder essentially composed of zirconium oxide.

[0045] "Molded body" refers to a composition having a certain shape composed of powder particles agglomerated by physical force, and in particular, a composition in a state where the shape is given (e.g., after molding) but not subjected to heat treatment. "Zirconium oxide molded body" refers to a molded body with zirconium oxide as the main component, and is a molded body essentially composed of zirconium oxide. In addition, molded body can be used interchangeably with "powder compact".

[0046] “Calcined body” refers to a composition having a certain shape composed of molten particles, and is a composition that has been heat treated at a temperature lower than the sintering temperature. “Zirconium oxide calcined body” refers to a calcined body having zirconium oxide as a main component, and is a calcined body essentially composed of zirconium oxide.

[0047] “Sintered body” refers to a composition having a certain shape and composed of crystal grains, and is a composition that has been heat treated at a temperature higher than the sintering temperature. “Zirconium oxide sintered body” refers to a sintered body having zirconium oxide as a main component, and is a sintered body essentially composed of zirconium oxide.

[0048] The "main component" refers to the component that constitutes the main phase (matrix, masterbatch, parent phase) in the composition of the composition, and preferably accounts for 75% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, or 99% by mass or more in the composition. In addition, the component that is 100% by mass or less than 100% by mass is preferably 75% by mass or more and 100% by mass or less, or 95% by mass or more and less than 100% by mass.

[0049] The “stabilizing element” refers to an element that stabilizes the crystal phase of zirconium oxide by being dissolved in zirconium oxide.

[0050] The "BET specific surface area" is a specific surface area [m 2 / g], in particular, the BET specific surface area measured under the following conditions.

[0051] Adsorption medium: N2

[0052] Adsorption temperature: -196℃

[0053] Pretreatment conditions: Degassing treatment at 250°C for more than 1 hour in an air atmosphere

[0054] The BET specific surface area can be measured using a conventional specific surface area measuring apparatus (for example, TRISTARII 3020, manufactured by Shimadzu Corporation).

[0055] In addition, the "air atmosphere" in the present embodiment includes a nitrogen atmosphere mainly containing nitrogen and oxygen and having an oxygen concentration of 18 to 23% by volume, and may contain moisture.

[0056] The "average particle size" is the D50 in the volume particle size distribution of the powder measured by the wet method, which can be measured using a conventional laser diffraction / scattering particle size distribution measuring device (e.g., MT3300EXII, manufactured by MicrotracBEL). The measurement sample is a slurry prepared by dispersing the slowly condensed powder in pure water by a dispersion treatment such as ultrasonic treatment. The measurement of the volume particle size distribution based on the wet method is preferably performed by making the slurry pH = 3.0 to 6.0.

[0057] The "average particle diameter" is D50 in the volume particle size distribution of the granular powder measured by a dry method, and can be measured using a conventional laser diffraction / scattering particle size distribution measuring device (e.g., MT3100II, manufactured by MicrotracBEL). The sample is not subjected to dispersion treatment such as ultrasonic treatment, and the granular powder in a slowly agglomerated state can be used directly.

[0058] The so-called "powder X-ray diffraction pattern" is an XRD pattern of a composition obtained by powder X-ray diffraction (hereinafter also referred to as "XRD") measurement under the following conditions, which is obtained by smoothing and background removal using an analysis program attached to the X-ray diffraction apparatus (for example, comprehensive powder X-ray analysis software PDXL Ver.2.2, manufactured by RIGAKU Corporation).

[0059] Radiation source: CuKα radiation (λ = 0.15418nm)

[0060] Measurement mode: continuous scan

[0061] Scanning speed: 2° / min

[0062] Measuring range: 2θ = 26° to 33°

[0063] 2θ=72°~76°

[0064] Accelerating voltage and current: 40mA and 40kV

[0065] Divergence longitudinal limiting slit: 10mm

[0066] Divergence / entrance slit: 1°

[0067] Light receiving slit: open

[0068] Detector: Semiconductor detector (D / teX Ultra)

[0069] Filter: Ni filter

[0070] Goniometer radius: 185mm

[0071] XRD measurement can be performed using a conventional X-ray diffraction device (e.g., Ultima IV, manufactured by RIGAKU). For a calcined body, the surface is ground using sandpaper with a particle size of #400 based on JIS R 6001-2, and then the calcined body is polished using a diamond abrasive with a particle size of 3 μm as a measurement sample, and the surface after polishing is subjected to XRD measurement. For a sintered body, the surface is ground to a surface roughness of Ra ≤ 0.02 μm as a measurement sample, and the surface after polishing is subjected to XRD measurement.

[0072] "XRD peak" means a peak having a peak top at 2θ detected in the XRD pattern obtained in the above XRD measurement. In the present embodiment, "having no XRD peak" means that the XRD peak is not detected in the above XRD measurement.

[0073] The XRD peak corresponding to each crystal plane of zirconium oxide is an XRD peak having a peak top at the following 2θ.

[0074] XRD peak corresponding to the monoclinic (111) plane: 2θ = 31 ± 0.5°

[0075] XRD peak corresponding to the monoclinic (11-1) plane: 2θ = 28 ± 0.5°

[0076] XRD peak corresponding to tetragonal (111) plane: 2θ = 30 ± 0.5°

[0077] XRD peak corresponding to cubic (111) plane: 2θ = 30 ± 0.5°

[0078] The XRD peak corresponding to the tetragonal (111) plane and the XRD peak corresponding to the cubic (111) plane were measured as one overlapping peak.

[0079] The "T+C phase ratio" refers to the ratio of the integrated intensity of the XRD peaks of tetragonal and cubic zirconia to the total integrated intensity of the XRD peaks of tetragonal, cubic and monoclinic zirconia in the XRD pattern obtained in the above XRD measurement, and is calculated by the following formula.

[0080] f T+C =[I t (111)+I c (111)]

[0081] / [I m (111)+I m (11-1)+I t (111)+I c (111)]

[0082] In the above formula, f T+Cis the tetragonal and cubic crystal ratio, I t (111) is the integrated intensity of the tetragonal (111) plane, I c (111) is the integrated intensity of the cubic crystal (111) plane, I m (111) is the integrated intensity of the monoclinic (111) plane, I m (11-1) is the integrated intensity of the monoclinic (11-1) plane, I t (111)+I c (111) corresponds to the integrated intensity of an XRD peak having a peak top at 2θ=30±0.5°.

[0083] The integrated intensity of each XRD peak is a value obtained by analyzing the XRD pattern using an analysis program attached to an X-ray diffractometer (for example, comprehensive powder X-ray analysis software PDXL Ver. 2.2, manufactured by RIGAKU Corporation).

[0084] The “measured density” is given by the relative volume of the sample [cm 3 ] mass [g] the value [g / cm 3 ]. The mass may be the value obtained by weighing the sample. Regarding the volume, for the molded body and the calcined body, the volume obtained by shape measurement may be used, and for the sintered body, the volume obtained by the Archimedes method according to JIS R 1634 may be used. The Archimedes method uses ion exchange water as a solvent, and the pretreatment may be performed by a boiling method. The measured densities of the molded body, the calcined body, and the sintered body are recorded as "molded body density", "calcined body density", and "sintered body density", respectively.

[0085] "Vickers hardness" is a value measured using a conventional Vickers hardness tester (e.g., device name: Q30A, manufactured by Qness) equipped with a diamond regular quadrangular pyramid indenter. The measurement is to statically press the indenter into the surface of the test sample and measure the diagonal length of the indentation formed on the surface of the test sample. Using the obtained diagonal length, the Vickers hardness can be calculated by the following formula.

[0086] Hv=F / {d 2 / 2sin(α / 2)}

[0087] In the above formula, Hv is the Vickers hardness (HV), F is the measurement load (1 kgf), d is the diagonal length of the indentation mark (mm), and α is the angle between the opposing surfaces of the indenter (136°).

[0088] As the measurement conditions of the Vickers hardness, the following conditions can be mentioned.

[0089] Test sample: disc-shaped with a thickness of 3.0±0.5mm

[0090] Measuring load: 1kgf

[0091] Before the measurement, the sample can be pre-treated, that is, the measurement surface can be polished with #800 water-resistant abrasive paper to remove the unevenness exceeding 0.1 mm. 10 points of the sample can be measured, and the average value can be used as the Vickers hardness.

[0092] The "total light transmittance" is the ratio [%] of the transmitted light (the sum of the linear transmitted light and the diffuse transmitted light) to the incident light, measured in accordance with JIS K 7361-1. The measurement sample is a disc-shaped sintered body with a sample thickness of 1.0±0.1 mm and a surface roughness Ra≤0.02 μm on both sides, and the measurement device is a haze meter with a D65 light source (for example, haze meter NDH4000, manufactured by Nippon Denshoku Co., Ltd.).

[0093] “Hue (L * 、a * 、b * )" is a value measured by the SCI method using a spectrophotometer (e.g., CM-700d, manufactured by Konica Minolta) having an illumination and light receiving optical system in accordance with geometric condition c of JIS Z 8722. As specific measurement conditions for the color tone, the following conditions can be cited in a method of measuring by arranging a white calibration plate as a background of the measurement sample (so-called white background measurement). Regarding the color tone of the sintered body, an arbitrary portion of the sintered body can be cut out in the horizontal direction and the measurement sample processed into a sample thickness of 1.0±0.1 mm can be measured.

[0094] Light source: D65 light source

[0095] Viewing angle: 2°

[0096] Measurement method: SCI

[0097] Brightness L * It is an index indicating brightness and has a value of 0 or more and 100 or less. * and b * Chroma C is an index indicating the color tone, and has a value of -100 or more and 100 or less. * It is an indicator of vividness.

[0098] The "three-point bending strength" is a value measured by a method in accordance with JIS R 1601. A test specimen is a columnar shape having a width of 4 mm, a thickness of 3 mm, and a length of 45 mm, and the distance between the supporting points is set to 30 mm. The test specimen is loaded in the horizontal direction.

[0099] “Pressureless sintering” refers to a method of sintering an object to be sintered (a molded body, a calcined body, etc.) by heating the object to be sintered at a temperature not lower than the sintering temperature of zirconium oxide (hereinafter also referred to as “sintering temperature”) without applying external force to the object to be sintered.

[0100] “Pressureless sintering” refers to a method of heating the object to be treated at a temperature lower than the sintering temperature without applying external force to the object to be treated during the heat treatment.

[0101] [Zirconium oxide composition]

[0102] This embodiment is a zirconium oxide composition, which comprises:

[0103] at least one first transition metal element selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd) and silver (Ag),

[0104] a coloring element of at least one of a lanthanide rare earth element and a second transition metal element of a type different from the first transition metal element, and

[0105] Zirconia containing stabilizing elements,

[0106] The content of the first transition metal element is 100 mass ppm or more,

[0107] The content of the second transition metal element is less than 100 mass ppm, and

[0108] The zirconium oxide composition satisfies at least any one of the following characteristics:

[0109] When measuring the characteristic X-ray of zirconium and the characteristic X-ray of the first transition metal element, the proportion of measurement points at which the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of zirconium is 0.05 or more is less than 3% of all the measurement points; and

[0110] When the characteristic X-rays of zirconium and the characteristic X-rays of the first transition metal element are measured, the distribution width of the ratio of the intensity of the characteristic X-rays of the first transition metal element to the intensity of the characteristic X-rays of zirconium is less than 0.3.

[0111] The first transition metal element (hereinafter also referred to as "M1 element") has the function of coloring zirconium oxide, serves as the basis of the color tone, and is contained in large quantities in the zirconium oxide composition of the present embodiment. It is preferably the transition metal element with the largest content contained in large quantities in the zirconium oxide composition of the present embodiment. The M1 element not only has a large influence on the thermal shrinkage behavior of the zirconium oxide composition, but also tends to segregate after sintering. However, by satisfying the constitution of the zirconium oxide composition of the present embodiment, the influence of the M1 element on the thermal shrinkage behavior can be significantly suppressed. As a result, the zirconium oxide composition of the present embodiment can be provided as a precursor of a calcined body in which the difference in mechanical strength between production batches is suppressed.

[0112] The zirconium oxide composition of the present embodiment is a zirconium oxide composition that can be a precursor of a calcined body, and is preferably at least one of a zirconium oxide powder and a zirconium oxide molded body. The zirconium oxide composition of the present embodiment may be a zirconium oxide molded body or a zirconium oxide powder.

[0113] The zirconium oxide composition of the present embodiment includes zirconium oxide containing a stabilizing element. The zirconium oxide containing a stabilizing element is preferably zirconium oxide in which the stabilizing element is solid-dissolved (stabilizing element solid-dissolved zirconium oxide). Therefore, the zirconium oxide composition of the present embodiment can be regarded as a zirconium oxide composition containing a stabilizing element, and further can be regarded as a stabilizing element solid-dissolved zirconium oxide composition.

[0114] The stabilizing element may be any element that does not color zirconium oxide but dissolves in zirconium oxide, and examples thereof include one or more selected from yttrium (Y), calcium (Ca) and magnesium (Mg), and yttrium is preferred.

[0115] The content of the stabilizing element in the zirconium oxide composition of the present embodiment (hereinafter also referred to as "stabilizing element amount", and when the stabilizing element is yttrium, it is also referred to as "yttrium amount") is sufficient as long as the crystal phase with tetragonal crystal as the main phase of the crystal phase of zirconium oxide is stabilized, and further the crystal phase containing tetragonal crystal and cubic crystal is stabilized, and can be exemplified by 2.0 mol% or more and 8.0 mol% or less. In addition, when the stabilizing element is yttrium, the stabilizing element amount (yttrium amount) can be 2.6 mol% or more, 3.1 mol% or more, 3.6 mol% or more, or 3.9 mol% or more, and can be 6.0 mol% or less, 5.6 mol% or less, 5.4 mol% or less, 4.3 mol% or less, or 4.1 mol% or less, preferably 2.6 mol% or more and 6.0 mol% or less, 3.6 mol% or more and 5.4 mol% or less, or 3.9 mol% or more and 4.1 mol% or less.

[0116] In the present embodiment, the amount of the stabilizing element is the molar ratio [mol %] of the stabilizing element converted into oxide to the total of zirconium oxide and the stabilizing element and lanthanide rare earth element converted into oxide. In terms of the oxide of the stabilizing element, yttrium is Y2O3, calcium is CaO, and magnesium is MgO.

[0117] The zirconium oxide composition of the present embodiment preferably does not contain undissolved stabilizing elements. The absence of undissolved stabilizing elements can be confirmed by the fact that the XRD pattern does not have an XRD peak derived from a compound of the stabilizing element. However, as long as it is within the range in which the effect of the zirconium oxide composition of the present embodiment is exerted, the presence of undissolved stabilizing elements may be permitted, that is, the presence of undissolved stabilizing elements may be permitted within the range in which no XRD peak derived from a compound of the stabilizing element is confirmed in the XRD pattern.

[0118] The zirconium oxide composition of the present embodiment contains one or more M1 elements selected from manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd) and silver (Ag). The M1 element is a transition metal element that has the function of coloring zirconium oxide and is easily segregated after sintering. The M1 element is an element that functions as a coloring component (main coloring component) that affects the tone of the hue of the sintered body obtained from the zirconium oxide composition of the present embodiment. In order to obtain a sintered body with a hue suitable for use as a dental restorative material, the zirconium oxide composition of the present embodiment preferably contains one transition metal element of more than 100 mass ppm, that is, one M1 element. On the other hand, in the case of containing two or more transition metal elements with a content of more than 100 mass ppm, for convenience, it is sufficient to distinguish the transition metal element with the largest content among the transition metal elements as the M1 element, and the other M1 elements as the first 'transition metal element (M1' element), the first "transition metal element (M1" element), etc.

[0119] The content of the M1 element (M1 element amount) of the zirconium oxide composition of the present embodiment is 100 mass ppm or more, and the more its content increases, the stronger the hue from the M1 element. The M1 element amount can be exemplified as 150 mass ppm or more, 300 mass ppm or more, or 500 mass ppm or more, and in addition, 0.2 mass % or less (2000 mass ppm or less), 0.15 mass % or less, 0.12 mass % or less, or 0.1 mass % or less (1000 mass ppm or less). The specific M1 element amount can be appropriately adjusted according to the target hue. For example, in the case of a hue suitable for use as a dental restorative material, as the M1 element amount, 100 mass ppm or more and 1500 mass ppm or less, 100 mass ppm or more and 1000 mass ppm or less, or 100 mass ppm or more and 500 mass ppm or less can be cited.

[0120] The amount of the M1 element in the present embodiment is the ratio [mass ppm] of the mass of the M1 element converted into oxide to the total mass of zirconium oxide and the metal element converted into oxide (hereinafter also referred to as “metal element mass”).

[0121] The type of M1 element can be appropriately selected according to the target color tone, for example, one or more selected from manganese, iron, cobalt, nickel, copper, molybdenum and silver can be cited, and one or more selected from manganese, iron, cobalt, nickel and copper can be cited, and one or more selected from manganese, iron and nickel can be cited, and at least one of manganese and iron can be cited, and at least one of iron and nickel can be cited, and iron can be cited. In addition, the M1 element can be manganese, iron, cobalt, nickel, copper, molybdenum or silver, manganese, iron, cobalt or nickel, and nickel or iron. For example, it can be cited respectively: in the case of obtaining a sintered body with a gray tone as the main tone, the M1 element is manganese; in the case of obtaining a sintered body with a yellow tone as the main tone, the M1 element is iron; in the case of obtaining a sintered body with a blue tone as the main tone, the M1 element is cobalt; and in the case of obtaining a sintered body with a green tone as the main tone, the M1 element is nickel.

[0122] The zirconium oxide composition of the present embodiment may contain the M1 element in any form. For example, the M1 element may be contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, halides, sulfates, nitrates, and acetates, further contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, and chlorides, further contained in the form of at least one of oxides and oxyhydroxides, and further contained in the form of oxides.

[0123] The zirconium oxide composition of the present embodiment satisfies at least any one of the following characteristics:

[0124] When measuring the characteristic X-ray of the zirconium element and the characteristic X-ray of the M1 element, the ratio of the intensity of the characteristic X-ray of the M1 element to the intensity of the characteristic X-ray of the zirconium element (hereinafter also referred to as "X-ray intensity ratio") is 0.05 or more, and the ratio of the measurement points of which the ratio of the intensity of the characteristic X-ray of the M1 element to the intensity of the characteristic X-ray of the zirconium element is 0.05 or less is 3% or less of all the measurement points (that is, the ratio of the number of measurement points with the X-ray intensity ratio of 0.05 or more in the total number of measurement points is 3% or less); and when measuring the characteristic X-ray of the zirconium element and the characteristic X-ray of the first transition metal element, the distribution width of the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of the zirconium element is 0.3 or less. It is considered that by satisfying such a configuration, the local presence of the M1 element is significantly reduced. As a result, it is considered that the local rapid thermal shrinkage caused by the uneven presence of the M1 element is suppressed, the hardness of the obtained calcined body becomes lower, and the deviation of the thermal shrinkage behavior caused by the difference in the production batch is suppressed. As a result, the hardness difference between the production batches of the calcined body obtained from the zirconium oxide composition of this embodiment can be suppressed.

[0125] The ratio of measurement points with an X-ray intensity ratio of 0.05 or more to all measurement points (hereinafter also referred to as "high intensity ratio") is preferably 3% or less, 2% or less, 0.5% or less, 0.1% or less, or 0.05% or less. The high intensity ratio may be 0% or more, more than 0%, or 0.01% or more, and is preferably 0% or more and 3% or less, more than 0% and 3% or less, or 0.01% or more and 0.5% or less.

[0126] In the zirconium oxide composition satisfying the strength ratio range described below, the high strength ratio may be any value, and examples thereof include 0% to less than 100%, 50% to 99.5%, or 80% to 99.5%.

[0127] The zirconium oxide composition of the present embodiment preferably does not have coarse agglomeration of the M1 element, and the ratio of the measurement points with an X-ray intensity ratio of 0.1 or more to all the measurement points (hereinafter also referred to as "coarse intensity ratio") is preferably 10% or less, 8% or less, 5% or less, 0.5% or less, 0.3% or less, 0.1% or less, or 0.01% or less. The coarse intensity ratio may be 0% or more or more than 0%, and is preferably 0% or more and 10% or less, more than 0% or more and 10% or less, or more than 0% or more and 5% or less. As the coarse intensity ratio when the M1 element is iron, 0% or more and 0.5% or less, or 0% or more and 0.01% or less can be exemplified.

[0128] The distribution width of the X-ray intensity ratio of the zirconium oxide composition of the present embodiment (i.e., the absolute value of the difference between the maximum intensity ratio (described later) and the minimum intensity ratio (described later); hereinafter also referred to as "intensity ratio range") is preferably 0.3 or less, 0.2 or less, 0.15 or less, 0.12 or less, 0.1 or less, or 0.08 or less. As a result, the obtained calcined body tends to have a more uniform hardness.

[0129] A narrow intensity ratio range means that the values ​​of the X-ray intensity ratios of all measuring points become equal, that is, the M1 element exists in the composition in a more uniform state. As a result, it is believed that the local rapid thermal shrinkage caused by the uneven presence of the M1 element is suppressed, the hardness of the obtained calcined body becomes lower, and the deviation of the thermal shrinkage behavior caused by the difference in the manufacturing batch is suppressed. Therefore, the zirconium oxide composition of the present embodiment preferably replaces the high strength ratio of 3% or less, or in addition to the high strength ratio of 3% or less, the intensity ratio range is the above value. The zirconium oxide composition of the present embodiment shows such an intensity ratio range, and the influence of the M1 element on the thermal shrinkage behavior of the zirconium oxide composition becomes more uniform. The intensity ratio range is greater than 0, greater than 0.01, greater than 0.04 or greater than 0.05. The intensity ratio range can be greater than 0 and less than 0.3, greater than 0 and less than 0.2, greater than 0.01 and less than 0.1, or greater than 0.04 and less than 0.08.

[0130] The intensity ratio range tends to be larger as the amount of the stabilizing element increases and the amount of the M1 element increases.

[0131] On the other hand, in a zirconium oxide composition in which the ratio of measurement points having an X-ray intensity ratio of 0.05 or more is less than 3% of all measurement points, the intensity ratio range may be any range, but preferably, the ratio of measurement points having an X-ray intensity ratio of 0.05 or more is less than 3% of all measurement points, and the intensity ratio range is less than 0.3.

[0132] The maximum value of the X-ray intensity ratio of the zirconium oxide composition of the present embodiment (hereinafter also referred to as the "maximum intensity ratio") is preferably less than 0.3, less than 0.2, or less than 0.1. By making the maximum intensity ratio within this range, the influence of the coarse agglomerated particles of the M1 element on the thermal shrinkage behavior of the zirconium oxide composition tends to become smaller. The maximum intensity ratio of the zirconium oxide composition of the present embodiment may be greater than 0.04 or greater than 0.05. As preferred maximum intensity ratios, 0.04 to 0.3, 0.04 to 0.2, or 0.05 to 0.1 may be cited.

[0133] The minimum value of the X-ray intensity ratio of the zirconium oxide composition of the present embodiment (hereinafter also referred to as "minimum intensity ratio") can be exemplified as 0 or more, more than 0, or more than 0.001. In addition, it can be 0.05 or less, 0.04 or less, 0.01 or less, or 0.002 or less. It can be exemplified as 0 or more and 0.01 or less, 0 or more and 0.002 or less, or more than 0 and 0.002 or less.

[0134] In the zirconium oxide composition of this embodiment, the characteristic X-rays of the zirconium element and the characteristic X-rays of the M1 element may be measured by field emission wavelength dispersive electron probe microanalyzer (hereinafter also referred to as "FE-EPMA") under the following conditions.

[0135] Accelerating voltage: 15 kV

[0136] Irradiation current: 50nA

[0137] Beam diameter: 1μm

[0138] Access time: 50msec

[0139] Magnification: 500 times

[0140] Analysis area: 256.0μm×256.0μm

[0141] In the measurement, a conventional FE-EPMA device (e.g., JXA-iHP200F, manufactured by JEOL Ltd.) is used, and the analysis area is divided into 65500±100 in a grid shape, and each obtained area is used as a measurement point. In the present embodiment, FE-EPMA measurement is performed on multiple locations (preferably 5±3 locations) of the same sample, and the high strength ratio, coarse strength ratio, maximum strength ratio, minimum strength ratio and strength ratio range are respectively obtained, and the average value thereof is used as the value of the present embodiment.

[0142] The zirconium oxide composition of the present embodiment contains a coloring element (hereinafter also referred to as a "secondary coloring component") of at least one of a lanthanide rare earth element and a second transition metal element different from the M1 element (hereinafter also referred to as an "M2 element"). The secondary coloring component is a coloring component for adjusting the color tone, and the zirconium oxide composition can adjust the color tone of the obtained sintered body by containing the secondary coloring component in addition to the M1 element. Depending on the desired color tone, the secondary coloring component may be only the lanthanide rare earth element, only the M2 element, or both the lanthanide rare earth element and the M2 element.

[0143] The transition metal element as the M2 element is a transition metal element of a different type from the M1 element contained in the composition of the present embodiment, and is a transition metal element having the function of coloring zirconium oxide and easily segregating after sintering. The M2 element is more preferably selected from one or more of manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver, and a transition metal element of a different type from the M1 element. The M2 element is more preferably selected from one or more of manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver, more preferably selected from one or more of manganese, iron, cobalt, nickel, copper, molybdenum and silver, further more preferably selected from one or more of manganese, iron, cobalt, nickel and copper, further more preferably selected from one or more of manganese, cobalt and nickel, further more preferably at least any one of manganese and cobalt, further more preferably cobalt.

[0144] The M2 element is preferably different from the M1 element and is manganese, iron, cobalt, nickel, copper, molybdenum or silver, further preferably different from the M1 element and is manganese, iron, cobalt, nickel or copper, further preferably different from the M1 element and is manganese, cobalt or nickel, further preferably different from the M1 element and is manganese or cobalt.

[0145] The content of the M2 element (M2 element amount) is less than 100 mass ppm, preferably less than 80 mass ppm, less than 70 mass ppm or less than 50 mass ppm. If it is such a content, the influence of the M2 element on the thermal shrinkage behavior of the zirconium oxide composition becomes very small. The zirconium oxide composition of the present embodiment may not contain the M2 element (that is, the content of the M2 element may be 0 mass ppm). Therefore, the M2 element amount of the zirconium oxide composition of the present embodiment is 0 mass ppm or more. On the other hand, the zirconium oxide composition of the present embodiment may contain the M2 element, and its content is more than 0 mass ppm, more than 3 mass ppm, more than 10 mass ppm, more than 20 mass ppm or more than 35 mass ppm, for example, more than 0 mass ppm and less than 100 mass ppm, more than 0 mass ppm and less than 80 mass ppm, or more than 0 mass ppm and less than 50 mass ppm. In addition, the M2 element amount can be more than 0 mass ppm and less than 10 mass ppm, or more than 0 mass ppm and less than 5 mass ppm.

[0146] The amount of the M2 element in the present embodiment is the mass ratio [mass ppm] of the M2 element converted into oxide to the mass of the metal element.

[0147] The conversions of the oxides of transition metal elements are: manganese is converted to Mn3O4, iron is converted to Fe2O3, cobalt is converted to Co3O4, nickel is converted to NiO, copper is converted to CuO, molybdenum is converted to Mo2O3, technetium is converted to Tc2O3, ruthenium is converted to RuO2, rhodium is converted to RhO2, palladium is converted to Pd2O3 and silver is converted to Ag2O.

[0148] The lanthanide rare earth element is preferably one or more selected from praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), erbium (Er) and ytterbium (Yb), more preferably one or more selected from praseodymium, neodymium, terbium and erbium, further preferably one or more selected from praseodymium, terbium and erbium, further more preferably at least any one of terbium and erbium, and particularly preferably erbium.

[0149] It is believed that lanthanide rare earth elements have less influence on the thermal shrinkage behavior of zirconium oxide compositions than transition metal elements. Therefore, the content of lanthanide rare earth elements is preferably less than 1.0 mass %, less than 0.85 mass %, less than 0.6 mass % or less than 0.15 mass %. The zirconium oxide composition of the present embodiment may not contain lanthanide rare earth elements (that is, the content of lanthanide rare earth elements may be 0 mass % or more than 0 mass %). On the other hand, the zirconium oxide composition of the present embodiment may contain lanthanide rare earth elements, and its content is more than 0 mass %, more than 0.01 mass % or more than 0.05 mass %, for example, 0 mass % or more and 1.0 mass % or less, 0 mass % or more and 0.15 mass % or more and 0.05 mass % or less. Lanthanide rare earth elements also function as stabilizing elements. However, in the present embodiment, for convenience, it is considered that lanthanide rare earth elements are not included in the stabilizing elements.

[0150] The content of the lanthanoid rare earth element may be determined as the ratio [mass %] of the lanthanoid rare earth element [g] calculated as oxide to the mass [g] of zirconium oxide or the metal element.

[0151] The oxide conversions of lanthanide rare earth elements are: praseodymium is Pr6O 11 , neodymium is Nd2O3, samarium is Sm2O3, europium is Eu2O3, gadolinium is Gd2O3, terbium is Tb4O7, erbium is Er2O3, and ytterbium is Yb2O3.

[0152] The zirconium oxide composition of the present embodiment may contain the secondary coloring component in any form. Examples of the secondary coloring component include: the secondary coloring component is contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, halides, sulfates, nitrates, and acetates, further contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, and chlorides, further contained in the form of at least one of oxides and oxyhydroxides, and further contained in the form of oxides.

[0153] In order to easily suppress abnormal grain growth during sintering, when the secondary coloring component is a lanthanide rare earth element, the lanthanide rare earth element is preferably dissolved in zirconium oxide (replaced with zirconium cations). The zirconium oxide composition of this embodiment preferably includes zirconium oxide in which a lanthanide rare earth element is dissolved in a solid state (hereinafter also referred to as "lanthanide element solid solution zirconium oxide") instead of, or in addition to, the lanthanide rare earth element. In particular, the zirconium oxide composition of this embodiment more preferably includes the lanthanide rare earth element only in the form of lanthanide element solid solution zirconium oxide, and further more preferably does not include a compound containing a lanthanide rare earth element such as a lanthanide rare earth oxide.

[0154] In the present embodiment, it may be determined that the compound containing the lanthanoid rare earth element is not contained by not observing the particulate lanthanoid rare earth element in FE-EPMA.

[0155] The zirconium oxide composition of the present embodiment may contain one or more third transition metal elements (hereinafter also referred to as "M3 elements") selected from titanium (Ti), vanadium (V) and niobium (Nb), preferably at least one of titanium and vanadium, and more preferably titanium. The M3 element is a transition metal element that is not easily segregated after sintering. By containing the M3 element in addition to the secondary coloring component or in place of the secondary coloring component, changes in the thermal shrinkage behavior of the zirconium oxide composition are suppressed, and the color tone of the obtained sintered body can be finely adjusted.

[0156] The zirconium oxide composition of the present embodiment may contain the M3 element, and its content may be 1.0 mass % or less, 0.5 mass % or less, or 0.3 mass % or less, and may be more than 0 mass % or more than 0.1 mass %. In addition, the zirconium oxide composition of the present embodiment may not contain the M3 element (that is, the content of the M3 element may be 0 mass % or more than 0 mass %). As the content of the M3 element of the present embodiment (M3 element amount), 0 mass % or more and 1.0 mass % or less, 0 mass % or more and 0.5 mass % or more and 0.05 mass % or less may be exemplified. In the case of containing the M3 element, more than 0 mass % and 1.0 mass % or less, more than 0 mass % and 0.5 mass % or more than 0 mass % and 0.05 mass % or less may be exemplified.

[0157] The content of the M3 element can be obtained as the mass ratio [mass %] of the M3 element [g] converted into oxides to the mass [g] of zirconium oxide and the metal element. The oxide conversions are: titanium is TiO2, vanadium is V2O5, and niobium is Nb2O3.

[0158] The zirconium oxide composition of the present embodiment only needs to contain the M3 element in any form. For example, the M3 element can be contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, halides, sulfates, nitrates, and acetates, further contained in the form of at least one selected from oxides, hydroxides, oxyhydroxides, and chlorides, further contained in the form of at least one of oxides and oxyhydroxides, and further contained in the form of oxides. In addition, part or all of the M3 element can be dissolved in zirconium oxide (can be substituted with zirconium cations).

[0159] The zirconium oxide composition of the present embodiment may contain one or more selected from aluminum oxide (Al2O3), silicon dioxide (SiO2) and zirconium oxide (Ge2O3) (hereinafter also referred to as "additive components"), and may further contain aluminum oxide. By including a trace amount of additive components, densification at low temperatures is easily promoted. When an additive component is included, its content may be more than 0 mass%, more than 0.005 mass% or more than 0.01 mass%, and may be less than 0.25 mass%, less than 0.2 mass%, less than 0.1 mass% or less than 0.06 mass%. In addition, the zirconium oxide composition of the present embodiment may not contain an additive component (that is, the content of the additive component may be 0 mass% or more).

[0160] The content of the additive component can be calculated as the mass ratio [mass %] of the additive component (Al2O3, SiO2 or Ge2O3) [g] relative to the mass of the metal element [g].

[0161] The zirconium oxide composition of the present embodiment preferably does not contain impurities, but may contain hafnium oxide (HfO2) as an inevitable impurity of zirconium oxide. The content of hafnium oxide as an inevitable impurity varies greatly depending on the raw material ore and the manufacturing method, and can be exemplified as 2.0 mass % or less. In the calculation of the density and other composition-based values ​​in the present embodiment, hafnium oxide can be regarded as zirconium oxide (ZrO2) for calculation.

[0162] The zirconia composition of the present embodiment may contain a binder (Japanese: 結合剤). By including a binder, the operability (handling) and shape retention become higher. The binder may be any binder that can be used for granulation and molding of ceramics, and an organic binder is preferred. As the organic binder, one or more selected from polyvinyl alcohol, polyvinyl butyral, wax, and acrylic resins are exemplified, preferably at least one of polyvinyl alcohol and acrylic resins, and more preferably acrylic resin. In the present embodiment, the acrylic resin is a polymer containing at least one of acrylate and methacrylate. As specific binders, for example, one or more selected from AS-1100, AS-1800, and AS-2000 (all are product names, manufactured by Toagosei Co., Ltd.) can be cited.

[0163] The content of the binder can be exemplified as 0.5 mass% or more, or 1 mass% or more, and further, 10 mass% or less, or 5 mass% or less.

[0164] For example, the composition of a yttrium-stabilized zirconia composition containing iron as the M1 element, cobalt as the M2 element, erbium as the lanthanide rare earth element, titanium as the M3 element, aluminum (aluminum oxide) as the additive component, and a binder can be obtained as follows.

[0165] Mass of metal element [g]:

[0166] Y2O3 + Er2O3 + ZrO2 + Al2O3 + Fe2O3 + Co3O4 + TiO2

[0167] Amount of stabilizing element [mol%]:

[0168] {(Y2O3 + Er2O3) / (Y2O3 + Er2O3 + ZrO2)} × 100

[0169] Erbium content [mass%]:

[0170] {Er2O3 / (Y2O3 + Er2O3 + ZrO2

[0171] + Al2O3 + Fe2O3 + Co3O4 + TiO2)} × 100

[0172] Iron content [mass%]:

[0173] {Fe2O3 / (Y2O3 + Er2O3 + ZrO2

[0174] + Al2O3 + Fe2O3 + Co3O4 + TiO2)} × 100

[0175] Cobalt content [mass%]:

[0176] {Co3O4 / (Y2O3+Er2O3+ZrO2

[0177] +Al2O3+Fe2O3+Co3O4+TiO2)}×100

[0178] Titanium content [mass %]:

[0179] {TiO2 / (Y2O3+Er2O3+ZrO2

[0180] +Al2O3+Fe2O3+Co3O4+TiO2)}×100

[0181] Alumina content [mass %]:

[0182] {Al2O3 / (Y2O3+Er2O3+ZrO2

[0183] +Al2O3+Fe2O3+Co3O4+TiO2)}×100

[0184] In addition, the content of the binder may be calculated by the following formula.

[0185] {(W1-W2) / W1}×100

[0186] In the above formula, W1 is the mass [g] of the zirconium oxide composition before heat treatment in an air atmosphere at 250° C. or higher and 400° C. or lower, and W2 is the mass [g] of the zirconium oxide composition before heat treatment in an air atmosphere at 250° C. or higher and 400° C. or lower. It should be noted that, due to different calculation methods, the total content of the zirconium oxide composition including the binder may not be 100% by mass in appearance.

[0187] The BET specific surface area of ​​the zirconium oxide composition of the present embodiment is 8 m 2 / g or above or 10m 2 / g or more, in addition, 15m 2 / g or less, 11m 2 / g or less or 10.5m 2 / g or less, preferably 8m 2 / g or more and 15m 2 / g or less, 10m 2 / g or more and 11m 2 / g or less, or 10m 2 / g or more and 10.5m 2 / g or less.

[0188] The average particle size of the zirconium oxide composition of the present embodiment is 0.35 μm or 0.4 μm or more, and 0.55 μm or 0.5 μm or less, and preferably 0.35 μm to 0.55 μm, or 0.4 μm to 0.5 μm or less.

[0189] The T+C phase ratio of the zirconium oxide composition of the present embodiment may be 50% or more, 55% or more, 60% or more, 70% or more, 80% or more, or 85% or more, and may be 100% or less, 99% or less, 95% or less, 92% or less, or 90% or less, and is preferably 50% or more and 100% or less, 70% or more and 95% or less, or 85% or more and 92% or less.

[0190] When the zirconium oxide composition of the present embodiment is in the form of a powder (hereinafter also referred to as "the powder of the present embodiment"), the powder may be a granular powder. This facilitates high fluidity and moldability.

[0191] The average particle diameter of the granular powder is 30 μm or more or 40 μm or more, and is 100 μm or less or 50 μm or less, and is preferably 40 μm or more and 50 μm or less.

[0192] The bulk density of the powder of this embodiment is 1.10 g / cm 3 Above, 1.15g / cm 3 Above or 1.20g / cm 3 Above, in addition, 1.40g / cm 3 Below, 1.35g / cm 3 Below or 1.30g / cm 3 Below, preferably 1.15 g / cm 3 Above and 1.40g / cm 3 Below, or 1.20g / cm 3 Above and 1.30g / cm 3 the following.

[0193] The zirconium oxide powder of this embodiment was filled into a mold with a diameter of 25 mm, subjected to uniaxial press molding at a pressure of 49 MPa, and then subjected to CIP treatment at a pressure of 196 MPa. The density was 3.2 g / cm 3 Above or 3.3g / cm 3 In addition, it can also be 3.5g / cm 3 Below or 3.4g / cm 3In particular, 3.0±0.1 g of the zirconium oxide powder of this embodiment is filled into a mold with a diameter of 25 mm, subjected to uniaxial press molding at a pressure of 49 MPa, and then subjected to CIP treatment at a pressure of 196 MPa. The measured density is 3.2 g / cm 3 Above or 3.3g / cm 3 Above, in addition, 3.5g / cm 3 Below or 3.4g / cm 3 Below, preferably 3.2 g / cm 3 Above and 3.5g / cm 3 Below, or 3.3g / cm 3 Above and 3.4g / cm 3 the following.

[0194] When the zirconium oxide composition of the present embodiment is a molded body (hereinafter also referred to as "the molded body of the present embodiment"), its actual measured density may be the same as the above-mentioned actual measured density, and can be exemplified as 3.2 g / cm 3 Above or 3.3g / cm 3 Above, in addition, 3.5g / cm 3 Below or 3.4g / cm 3 Below, preferably 3.2 g / cm 3 Above and 3.5g / cm 3 Below, or 3.3g / cm 3 Above and 3.4g / cm 3 the following.

[0195] The shape of the molded body of the present embodiment may be the same as the shape of the target calcined body, and may be, for example, one or more selected from a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, a cone, a sphere, and a substantially spherical shape, and may further be any shape such as the shape of a dental restorative material.

[0196] The molded body of the present embodiment only needs to have a hardness that is not easily damaged during handling. For example, the Vickers hardness can be 10.0 HV or more, 11.0 HV or more, or 11.5 HV or more. In addition, it is 14.0 HV or less, 13.0 HV or less, or 12.0 HV or less. It can be 10.0 HV or more and 14.0 HV or less, 11.0 HV or more and 13.0 HV or less, or 11.5 HV or more and 12.0 HV or less. If the Vickers hardness is 11.0 or more, defects during handling are less likely to occur.

[0197] The molded body of the present embodiment is obtained by molding the powder of the present embodiment, but the values ​​of the high strength ratio and the like measured by FE-EPMA, the composition, the BET specific surface area, and the like do not change before and after molding.

[0198] The zirconium oxide composition of the present embodiment can be used for known uses of zirconium oxide, and is preferably used as a precursor of at least one of a sintered body and a pre-calcined body, and is preferably used as at least one of a dental material and a precursor thereof.

[0199] [Method for producing zirconium oxide composition]

[0200] The method for producing the zirconium oxide composition of the present embodiment may be any method as long as it can produce a zirconium oxide composition satisfying the above-mentioned structure.

[0201] As a preferred production method when the zirconium oxide composition of the present embodiment is a powder, there can be mentioned a production method of a zirconium oxide composition (zirconium oxide powder) having a mixing step, in which the following zirconium oxide powders are mixed so that the content of the following M1 element is 100 mass ppm or more and the content of the following M2 element is less than 100 mass ppm:

[0202] A zirconium oxide powder comprising one or more M1 elements selected from the group consisting of manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver and zirconium oxide containing a stabilizing element, wherein the ratio of the intensity of the characteristic X-ray of the M1 element to the intensity of the characteristic X-ray of the zirconium element when measuring the characteristic X-ray of the zirconium element and the characteristic X-ray of the M1 element is 0.05 or more is 2% or less of all the measuring points, and

[0203] A zirconium oxide powder containing at least one coloring element of a lanthanoid rare earth element and an M2 element different in kind from the M1 element, and zirconium oxide.

[0204] In the mixing step, the following zirconium oxide powder is mixed: a zirconium oxide powder containing one or more M1 elements selected from manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver and a stabilizing element, wherein the ratio of the intensity of the characteristic X-ray of the M1 element to the intensity of the characteristic X-ray of the zirconium element when the characteristic X-ray of the zirconium element and the characteristic X-ray of the M1 element are measured is 2% or less of all the measurement points (hereinafter also referred to as "raw material powder 1"), and a zirconium oxide powder containing at least one of a lanthanide rare earth element and an M2 element different from the M1 element, and zirconium oxide (hereinafter also referred to as "raw material powder 2") are mixed. Unlike the case where the zirconium oxide powder and the compound of the M1 element are directly mixed to obtain a mixed powder, in the manufacturing method of the present embodiment, zirconium oxide containing the M1 element and the like is used as a starting material in advance. As a result, even if dry mixing or other simple mixing methods are used, the M1 element and the coloring element are easily made more uniform.

[0205] The raw material powder 1 contains the M1 element. The M1 element contained in the raw material powder 1 may be the same as the M1 element in the zirconium oxide composition of the present embodiment.

[0206] In order to make the content of M1 element in the zirconium oxide composition obtained by the mixing process be 100 mass ppm or more, the content of M1 element in the raw powder 1 only needs to be the same as the amount of M1 element in the zirconium oxide composition of the present embodiment described above, for example, it can be more than 0.01 mass% (more than 100 mass ppm), more than 0.05 mass% (more than 500 mass ppm) or more than 0.1 mass% (more than 1000 mass ppm), and further, it can be less than 0.3 mass% (more than 3000 mass ppm), less than 0.25 mass% (less than 2500 mass ppm) or less than 0.2 mass% (less than 2000 mass ppm).

[0207] In the raw material powder 1, when the characteristic X-ray of the zirconium element and the characteristic X-ray of the M1 element are measured, the ratio of the intensity of the characteristic X-ray of the M1 element to the intensity of the characteristic X-ray of the zirconium element (X-ray intensity ratio) is 0.05 or more (high intensity ratio) is less than 2% of all the measurement points. It is considered that by satisfying such a high intensity ratio, the aggregation of the M1 element in the raw material powder 1 is also reduced.

[0208] The high strength ratio in the raw material powder 1 can be exemplified as 2% or less, 1% or less, or 0.1% or more, more than 0%, or more than 0.01%, and can be exemplified as 0% or more and 2% or less, more than 0% and 1% or less, or 0.01% or more and 0.1% or less.

[0209] The raw material powder 1 preferably does not have coarse agglomeration of the M1 element, and the ratio of the measurement points where the X-ray intensity ratio is 0.1 or more (coarse intensity ratio) is preferably 0.5% or less, 0.1% or less, or 0.05% or less. The coarse intensity ratio may be 0% or more or more than 0%, preferably 0% or more and 0.5% or less, or 0% or more and 0.05% or less.

[0210] The characteristic X-rays of the zirconium element and the characteristic X-rays of the M1 element in the raw material powder 1 of the present embodiment may be measured by the same FE-EPMA measurement as that of the zirconium oxide composition of the present embodiment except that the following conditions are adopted.

[0211] Accelerating voltage: 15 kV

[0212] Irradiation current: 50nA

[0213] Beam diameter: 1μm

[0214] Access time: 50msec

[0215] Magnification: 5000 times

[0216] Analysis area: 45.32μm×45.32μm

[0217] The maximum value of the X-ray intensity ratio of the raw material powder 1 (maximum intensity ratio) is preferably 0.9 or less, 0.5 or less, or 0.2 or less. By setting the X-ray intensity ratio to this range, it is not easy to produce aggregation of the M1 element in the zirconium oxide composition of the present embodiment. The maximum intensity ratio of the raw material powder 1 can be 0.05 or more or 0.08 or more, and can be 0.05 or more and 0.9 or less, or 0.08 or more and 0.2 or less.

[0218] The minimum intensity ratio of the X-ray intensity ratio of the raw material powder 1 may be 0 or more or more than 0 and 0.01 or less, and may be 0 or more and 0.01 or less, or more than 0 and 0.01 or less.

[0219] For the same reason as the intensity ratio range in the zirconium oxide composition of the present embodiment, the distribution width (intensity ratio range) of the X-ray intensity ratio of the raw powder 1 is less than 0.9, less than 0.5 or less than 0.2, and may be greater than 0 or greater than 0.01, and may be exemplified as greater than 0 and less than 0.9, or greater than 0.01 and less than 0.2.

[0220] The raw material powder 1 contains zirconium oxide containing a stabilizing element. The type and content of the stabilizing element may be the same as those of the zirconium oxide containing a stabilizing element contained in the zirconium oxide composition of the present embodiment.

[0221] The raw material powder 2 contains at least one coloring element (secondary coloring component) of a lanthanoid rare earth element and an M2 element different from the M1 element. Preferred secondary coloring components contained in the raw material powder 2 may be the same as those in the zirconium oxide composition of this embodiment.

[0222] The content of the M2 element in the raw material powder 2 can be the same value as the M2 element amount in the zirconium oxide composition of the present embodiment described above, and can be, for example, 800 mass ppm or less, 500 mass ppm or less, or 100 mass ppm or less, and can also be greater than 0 mass ppm, 10 mass ppm or more, or 30 mass ppm or more.

[0223] The preferred content of lanthanide rare earth elements contained in the raw material powder 2 only needs to be the same value as the content of lanthanide rare earth elements in the zirconium oxide composition of the present embodiment described above, and can be exemplified by being 4 mass % or more, 6 mass % or more, or 8 mass % or less, and 20 mass % or less, 15 mass % or less, 12 mass % or less, or 10 mass % or less.

[0224] The raw material powder 2 contains zirconium oxide. When the secondary coloring component is the M2 element, the zirconium oxide is preferably zirconium oxide containing a stabilizing element. On the other hand, when the secondary coloring component is a lanthanide rare earth element, the zirconium oxide is preferably a lanthanide rare earth element solid solution zirconium oxide.

[0225] When the zirconium oxide contained in the raw material powder 2 is zirconium oxide containing a stabilizing element, the type and content of the stabilizing element may be the same as those of the zirconium oxide containing a stabilizing element contained in the zirconium oxide composition of the present embodiment.

[0226] When the zirconium oxide contained in the raw material powder 2 is zirconium oxide containing a stabilizing element, the amount of the stabilizing element in the raw material powders 1 and 2 is preferably the same. For example, the difference in the amount of the stabilizing element between the raw material powders 1 and 2 may be 1.5 mol% or less or 1.0 mol% or less, or 0 mol% or more. On the other hand, when the raw material powder 2 contains a lanthanide rare earth element, the difference in the amount of the stabilizing element between the raw material powders 1 and 2 is equal to the amount of the stabilizing element in the raw material powder 1.

[0227] In order to achieve the target content of M1 element and coloring element, in the mixing step, it is preferred to further mix, in addition to raw material powder 1 and raw material powder 2, a powder of zirconium oxide containing stabilizing elements that does not contain transition metal elements and lanthanide rare earth elements (hereinafter also referred to as "raw material powder 3").

[0228] The raw material powder 3 is a stabilizing element-containing zirconium oxide powder that does not contain a transition metal element or a lanthanoid rare earth element, and is preferably an yttrium-containing zirconium oxide powder that does not contain a transition metal element or a lanthanoid rare earth element.

[0229] The amount of the stabilizing element in the raw material powder 3 may be the same as that of the raw material powder 1 and the zirconium oxide composition of the present embodiment in terms of the type and content of the stabilizing element.

[0230] In the mixing step, in addition to the raw material powders 1 to 3, an M3 element source may be supplied. As the M3 element source, at least one of salts and compounds containing one or more selected from titanium, vanadium and niobium may be cited, and one or more selected from oxides, hydroxides, oxyhydroxides, halides, carbonates, sulfates, nitrates and acetates containing one or more selected from titanium, vanadium and niobium may be exemplified, preferably one or more selected from oxides, hydroxides, oxyhydroxides, chlorides and acetates containing one or more selected from titanium, vanadium and niobium, and more preferably at least one of oxides and hydroxides containing one or more selected from titanium, vanadium and niobium.

[0231] As titanium sources, for example, one or more selected from titanium oxide (TiO2), titanium hydroxide (Ti(OH)2), titanium oxide (TiOOH), titanium (II) chloride (TiCl2), titanium (III) chloride (TiCl3), titanium (IV) chloride (TiCl4), titanium sulfate (Ti(SO4)2), titanium nitrate (Ti(NO3)2) and titanium acetate (Ti(CH3COO)4) can be cited.

[0232] As vanadium sources, for example, one or more selected from vanadium oxide (VO), vanadium pentoxide (V2O5), vanadium hydroxide (V(OH)2), vanadium oxyhydroxy (VO(OH)2), vanadium (III) chloride (VCl3), vanadium sulfate (V2(SO4)3) and vanadium acetate (V(CH3COO)4) can be mentioned.

[0233] Examples of the niobium source include one or more selected from niobium oxide (Nb2O5), vanadium hydroxide (V(OH)5), niobium (V) chloride (Nbl5) and niobium acetate (V(CH3COO)3).

[0234] The M3 element source may be mixed so that the zirconium oxide composition obtained by the mixing step has a content equivalent to the content of the M3 element in the zirconium oxide composition of the present embodiment described above.

[0235] In addition, in addition to or instead of the M3 element source, at least any one of the raw material powders 1 to 3 may contain the M3 element.

[0236] In the mixing step, in addition to the raw material powders 1 to 3, an additive component source may be supplied.

[0237] As the source of the additive component, at least any one of salts and compounds containing one or more selected from aluminum, silicon and germanium can be cited, and one or more selected from oxides, hydroxides, oxyhydroxides, halides, carbonates, sulfates, nitrates and acetates containing one or more selected from aluminum, silicon and germanium can be exemplified. As a preferred source of the additive component, one or more selected from aluminum oxide, silicon dioxide and germanium oxide can be cited, and aluminum oxide is further cited.

[0238] The source of the additive component may be mixed so that the zirconium oxide composition obtained by the mixing step has a content equivalent to the content of the additive component in the zirconium oxide composition of the present embodiment described above.

[0239] Furthermore, in addition to or in place of the additive component source, at least any one of the raw material powders 1 to 3 may contain an additive component.

[0240] The raw material powders 1 to 3 may contain a binder. By containing a binder, the workability (handling) and shape retention are further improved. The binder and its content may be the same as the binder contained in the zirconium oxide composition of the present embodiment.

[0241] The starting materials such as raw material powders 1 to 3 preferably have the same physical properties as the zirconium oxide powder of the present embodiment, and the starting materials preferably have the same physical properties as each other. The following physical properties can be cited as the physical properties of the starting materials.

[0242] The BET specific surface area of ​​each starting material is preferably 8 m 2 / g or above or 10m 2 / g or more, in addition, 15m 2 / g or less, 12m 2 / g or less, 11m 2 / g or less or 10.5m 2 / g or less, 8m 2 / g or more and 15m 2 / g or less, or 10m 2 / g or more and 12m 2 / g or less.

[0243] The average particle size of each starting material is preferably 0.35 μm or 0.4 μm or more, and more preferably 0.55 μm or 0.5 μm or less, and examples thereof include 0.35 μm to 0.55 μm, or 0.4 μm to 0.5 μm or less.

[0244] The T+C phase ratio of each starting material is preferably 50% or more, 55% or more, or 60% or more, and is preferably 100% or less, 99% or less, 95% or less, 92% or less, or 90% or less.

[0245] Each starting material is preferably a granular powder. The average particle diameter of the granular powder is 30 μm or more or 40 μm or more, and 100 μm or less or 50 μm or less, preferably 30 μm or more and 100 μm or more and 40 μm or more and 50 μm or less.

[0246] In the mixing step, the starting materials may be mixed so that the content of the M1 element is 100 mass ppm or more and the content of the M2 element is less than 100 mass ppm. The content of M1 and the coloring element may be equal to the content of the zirconium oxide composition of the present embodiment.

[0247] The mixing method may be any mixing method that makes the starting materials uniform, and may be at least one of dry mixing and wet mixing, or dry mixing. In the manufacturing method of this embodiment, the zirconium oxide powders containing the M1 element and the coloring component are mixed with each other in advance, so even if a simple mixing method such as shaking or stirring mixing is used, it is not easy to cause local presence of the M1 element.

[0248] The mixing ratio of each starting material may be a desired mixing ratio according to the target content of the M1 element and the target color tone. For example, each starting material may be mixed at the following ratio so that the total is 100 mass %.

[0249] Raw material powder 1: 15 mass % or more, 18 mass % or more, or 20 mass % or more,

[0250] 80% by mass or less, 75% by mass or less, or 70% by mass or less;

[0251] Raw material powder 2 containing M2 element:

[0252] 0% by mass or more, more than 0% by mass, 1% by mass or more, 3% by mass or more, or 5% by mass or more,

[0253] 30% by mass or less, 20% by mass or less, or 18% by mass or less;

[0254] Raw material powder 2 containing lanthanide rare earth elements:

[0255] 0% by mass or more, more than 0% by mass, 0.5% by mass or more, 0.8% by mass or more, or 1% by mass or more,

[0256] 10% by mass or less, 8% by mass or less, or 3% by mass or less;

[0257] Raw material powder 3: 15 mass % or more, 18 mass % or more, or 20 mass % or more, and 80 mass % or less, 75 mass % or less, or 70 mass % or less;

[0258] M3 element source: 0 mass % or more, more than 0 mass %, 0.05 mass % or more, 0.10 mass % or more, or 0.20 mass % or more,

[0259] 1.0 mass % or less, 0.8 mass % or less, or 0.7 mass % or less;

[0260] Additive source: 0 mass % or more, more than 0 mass %, 0.003 mass % or more, or 0.01 mass % or more,

[0261] 0.1 mass % or less, 0.08 mass % or less, or 0.06 mass % or less.

[0262] When the zirconium oxide composition of the present embodiment is a molded body (powder compact), a preferred method for producing a zirconium oxide composition (zirconia molded body) includes a molding step of molding the zirconium oxide powder obtained by the mixing step.

[0263] The molding method may be any molding method that can make a zirconium oxide composition (zirconium oxide powder) into a powder compact, and examples thereof include one or more methods selected from uniaxial press molding, cold isostatic pressing (hereinafter also referred to as "CIP") treatment, slip casting, sheet molding, slip casting (Japanese: slurry casting) and injection molding, preferably one or more methods selected from slip casting, injection molding, uniaxial press molding and CIP treatment, more preferably at least one of uniaxial press molding and CIP treatment, and further preferably a method of uniaxially press molding the zirconium oxide composition and CIP treatment the obtained primary molded body. The pressure in the uniaxial press molding may be exemplified as: 15 MPa or more or 90 MPa or more, and further, 400 MPa or less or 150 MPa or less.

[0264] [Method for producing raw material powder]

[0265] As a preferred method for producing the raw material powder 1, there can be cited a method having a step of drying a slurry containing hydrated zirconium oxide, a stabilizing element source and an M1 element source to obtain a dry powder, and a heat treatment step of heat-treating the dry powder at a temperature lower than the sintering temperature. When powdered zirconium oxide is mixed with an M1 element source, localization of the M1 element is likely to occur. The localized M1 element, even if, for example, below the measurement limit, will have a great influence on the thermal shrinkage behavior of the obtained zirconium oxide composition. In contrast, it is believed that by mixing zirconium oxide with an M1 element source at the stage of a precursor of the powder, the localization of the M1 element that can affect the shrinkage behavior of the zirconium oxide composition can be suppressed. The raw material powder 1 is preferably a powder obtained from a solution containing a precursor of zirconium oxide and an M1 element, and is more preferably a powder having at least one of a hydrolyzate and a coprecipitate obtained from a solution containing hydrated zirconium oxide and an M1 element as a precursor, or is more preferably a powder having a hydrolyzate obtained from a solution containing hydrated zirconium oxide and an M1 element as a precursor.

[0266] In the step of drying a solution containing hydrated zirconium oxide, a stabilizing element source, and an M1 element source to obtain a dry powder (hereinafter also referred to as a "precursor synthesis step"), a solution containing hydrated zirconium oxide, a stabilizing element source, and an M1 element source (hereinafter also referred to as a "raw material solution") is supplied. The contents of hydrated zirconium oxide, a stabilizing element source, and an M1 element source contained in the raw material solution may be the same as the composition of the raw material powder 1.

[0267] In order to make hydrated zirconium oxide more easily dispersed, the pH of the raw material solution is preferably 7 or less or 5 or less, and may be 1 or more or 3 or more.

[0268] The hydrated zirconium oxide is zirconium oxide in a hydrated state (ZrO2·nH2O, where n is an integer), and is more preferably a hydrated zirconium oxide sol. The hydrated zirconium oxide is preferably a hydrated zirconium oxide obtained by one or more selected from the group consisting of hydrolysis, coprecipitation and neutralization of a zirconium salt, preferably a hydrated zirconium oxide obtained by hydrolysis, preferably a hydrated zirconium oxide obtained by hydrolysis or coprecipitation of one or more selected from the group consisting of zirconium oxychloride, zirconium oxynitrate, zirconium chloride and zirconium sulfate, and preferably a hydrated zirconium oxide obtained by hydrolysis or coprecipitation of zirconium oxychloride.

[0269] The stabilizing element source (hereinafter, when the stabilizing element is yttrium, etc., it is also referred to as "yttrium source" etc.) can be at least any one of the salts and compounds containing the stabilizing element, and can include one or more selected from the oxides, hydroxides, oxyhydroxyls, halides, carbonates, sulfates, nitrates and acetates containing the stabilizing element, more preferably at least any one of the oxides, hydroxides and chlorides containing the stabilizing element, and even more preferably a chloride containing the stabilizing element.

[0270] As the yttrium source, one or more selected from yttrium oxide, yttrium hydroxide, yttrium oxyhydroxide, yttrium chloride, yttrium carbonate, yttrium sulfate, yttrium nitrate and yttrium acetate can be cited, and further one or more selected from yttrium oxide, yttrium hydroxide, yttrium oxyhydroxide and yttrium chloride can be cited, and further at least any one of yttrium oxide and yttrium chloride can be cited, preferably yttrium chloride.

[0271] As the calcium source, for example, one or more selected from calcium oxide, calcium hydroxide, calcium oxyhydroxide, calcium chloride, calcium carbonate, calcium sulfate, calcium nitrate and calcium acetate can be mentioned, further one or more selected from calcium oxide, calcium hydroxide, calcium oxyhydroxide and calcium chloride can be mentioned, and further at least any one of calcium oxide and calcium chloride can be mentioned.

[0272] As the magnesium source, for example, one or more selected from magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide, magnesium chloride, magnesium carbonate, magnesium sulfate, magnesium nitrate and magnesium acetate can be cited, further one or more selected from magnesium oxide, magnesium hydroxide, magnesium oxyhydroxide and magnesium chloride can be cited, and further at least any one of magnesium oxide and magnesium chloride can be cited.

[0273] The M1 element source (hereinafter, when the M1 element is iron, etc., it is also referred to as "iron source" etc.) can be at least any one of the salts and compounds containing the M1 element, and can include one or more selected from the oxides, hydroxides, oxyhydroxides, halides, carbonates, sulfates, nitrates and acetates containing the M1 element, more preferably at least any one of the oxides, hydroxides and chlorides containing the M1 element, and further preferably an oxide containing the M1 element. As the main M1 source, the following substances can be mentioned.

[0274] As the manganese source, for example, one or more selected from manganese (II) oxide (MnO), manganese (III) oxide (Mn2O3), manganese dioxide (MnO2), trimanganese tetraoxide (Mn3O4), manganese hydroxide (Mn(OH)2), manganese oxyhydroxide (MnOOH), manganese chloride (MnCl2), manganese carbonate (MnCO3), manganese sulfate (MnSO4), manganese nitrate (Mn(NO3)2) and manganese acetate (Mn(COOH)2) can be mentioned, and at least one of manganese hydroxide and manganese acetate can be further mentioned.

[0275] As the iron source, for example, one or more selected from iron (II) oxide (FeO), iron (III) oxide (Fe2O3), ferroferric oxide (Fe3O4), iron (II) hydroxide (Fe(OH)2), iron (III) hydroxide (Fe(OH)3), iron (II) chloride (FeCl2) and iron (III) chloride (FeCl3), and iron carbonate (FeCO3) can be cited, and preferably one or more selected from iron (III) hydroxide, iron (II) hydroxide, iron (III) chloride and iron (II) chloride.

[0276] As a cobalt source, for example, one or more selected from cobalt (II) oxide (CoO), cobalt (IV) oxide (CoO2), cobalt trioxide (Co3O4), cobalt hydroxide (Co(OH)2), cobalt oxyhydroxide (CoOOH), cobalt chloride (CoCl2), cobalt carbonate (CoCO3), cobalt sulfate (CoSO4), cobalt nitrate (Co(NO3)2) and cobalt acetate (Co(CH3OO)2) can be cited.

[0277] As a nickel source, for example, one or more selected from nickel (II) oxide (NiO), nickel (IV) oxide (NiO2), nickel tetraoxide (Ni3O4), nickel hydroxide (Ni(OH)2), nickel oxyhydroxide (NiOOH), nickel chloride (NiCl2), nickel carbonate (NiCO3), nickel sulfate (NiSO4), nickel nitrate (Ni(NO3)2) and nickel acetate (Ni(CH3COO)2) can be cited.

[0278] As the copper source, for example, one or more selected from copper (II) oxide (CuO), copper (IV) oxide (CuO2), cupric oxide (Cu3O4), copper hydroxide (Cu(OH)2), copper oxyhydroxide (CuOOH), copper chloride (CuCl2), copper carbonate (CuCO3), copper sulfate (CuSO4), copper nitrate (Cu(NO3)2) and copper acetate (Cu(CH3COO)2) can be mentioned.

[0279] The solvent contained in the raw material solution may be any solvent that disperses the hydrated zirconium oxide, and may be at least one of a polar solvent and a non-polar solvent, preferably at least one of alcohol and water, more preferably at least one of ethanol and water, and still more preferably water. As the water contained in the raw material composition, at least one of pure water and ion exchange water may be exemplified. In addition, a solution containing hydrated zirconium oxide and a solvent thereof obtained by hydrolyzing, coprecipitating and neutralizing a zirconium salt may be supplied as the hydrated zirconium oxide and the solvent.

[0280] In the case where the raw material powder 1 contains the M3 element, the raw material solution may contain the above-mentioned M3 element source.

[0281] The raw material solution can be obtained by any method as long as the hydrated zirconium oxide, the stabilizing element source and the M1 element source are uniformly mixed. As the method for producing the raw material solution, for example, there can be exemplified: (1) a method of mixing hydrated zirconium oxide, a stabilizing element source, an M1 element source and a solvent; (2) a method of mixing a hydrated zirconium oxide solution with a stabilizing element source and an M1 element source; (3) a method of mixing a hydrated zirconium oxide solution, a solution containing a stabilizing element source and a solution containing an M1 element source. As a preferred mixing method, there can be cited a manufacturing method having a step of mixing a hydrated zirconium oxide solution, a solution containing an M1 element source and a stabilizing element source, and further a manufacturing method having a step of mixing a hydrated zirconium oxide solution obtained by hydrolyzing a zirconium salt, a solution containing an M1 element source and a stabilizing element source.

[0282] The drying method in the drying process can be any known method for removing the solvent and the hydration water of hydrated zirconium oxide from the raw material solution. Thus, a dried powder is obtained. As a drying method, any drying method can be selected according to the concentration and amount of the raw material solution provided in the drying process. In addition, as drying conditions, the following conditions can be cited.

[0283] Dry atmosphere: air atmosphere, preferably air circulation atmosphere

[0284] Drying temperature: above 150℃, above 160℃ or above 180℃, and

[0285] 210℃ or less, 200℃ or less, or 190℃ or less

[0286] The drying method and drying time of the raw material solution can be appropriately set according to the amount of the raw material solution to be processed and the form and characteristics of the drying furnace. As the drying time, more than 5 hours or more than 10 hours can be mentioned, and in addition less than 75 hours or less than 50 hours can be mentioned.

[0287] The method for producing the raw material powder 1 includes a heat treatment step of heat-treating the dry powder at a temperature lower than the sintering temperature. Through such heat treatment, the stabilizing element is efficiently dissolved in the zirconium oxide to obtain the raw material powder 1. In addition, by undergoing such a thermal history before forming a molded body (powder compact), the aggregation of the M1 element during the heat treatment after molding can be further suppressed.

[0288] The heat treatment temperature in the heat treatment is a temperature that promotes the solid solution of the stabilizing elements into the zirconium oxide, and any temperature lower than the sintering temperature can be used in a manner to achieve the desired BET specific surface area. There is a tendency that the higher the heat treatment temperature, the lower the BET specific surface area. As the heat treatment temperature, 1200°C or less, less than 1200°C or less than 1150°C can be exemplified. In order to further promote the solid solution of the stabilizing elements into the zirconium oxide, the heat treatment temperature is preferably above 1000°C, above 1050°C or above 1100°C.

[0289] The heat treatment conditions other than the heat treatment temperature may be any conditions that promote the solid solution of the stabilizing element in zirconium oxide, and the following conditions can be exemplified.

[0290] Heat treatment atmosphere: oxidizing atmosphere, preferably air atmosphere,

[0291] Heat treatment temperature: above 1000℃, above 1025℃ or above 1050℃, and

[0292] Below 1200℃ or below 1150℃

[0293] The heat treatment time can be appropriately adjusted depending on the amount of dry powder to be heat treated and the type and characteristics of the heat treatment furnace used, and can be 30 minutes or more or 1 hour or more and 10 hours or less or 5 hours or less.

[0294] When the raw material powder 1 contains an additive component, the above-mentioned additive component source can be mixed with the raw material powder 1 after heat treatment. The mixing method can be any known method, and it can also be performed simultaneously with the pulverization step described later. The amount of the additive component source contained in the raw material powder 1 can be the same as the amount of the above-mentioned additive component.

[0295] In order to adjust the particle size of the raw material powder 1, the method for producing the raw material powder 1 may include a step of crushing the powder (hereinafter also referred to as a "crushing step"). The crushing may be appropriately performed by a method in which the powder has a desired particle size, and may be at least one of dry crushing and wet crushing. From the perspective of high crushing efficiency, the crushing is preferably wet crushing, more preferably crushing using one or more selected from a vibration mill, a ball mill, and a bead mill, and further preferably crushing using a ball mill and a bead mill.

[0296] The pulverization time may be appropriately set according to the amount of the calcined powder to be supplied to the pulverization step and the pulverization method. The longer the pulverization time, the smaller the particle size until it reaches an equilibrium size.

[0297] In order to control the fluidity of the powder or improve the formability, the method for producing the raw powder 1 may include a step of granulating the powder to obtain a granular powder (hereinafter also referred to as a "granulation step"). Granulation is any method in which the secondary particles of the powder slowly agglomerate with each other to form granular particles. As a granulation method, one or more selected from spray drying, stirring granulation and extrusion granulation can be cited, and further a spray drying method can be cited. In the spray drying method, a slurry obtained by dispersing the granulated powder in a solvent is made into droplets, which are spray-dried to obtain granular powder. The above-mentioned solvent may be at least any one of water and alcohol. In addition, it is also possible to granulate the slurry by mixing a binder such as an acrylic resin in the slurry as needed and then spray drying it.

[0298] The raw material powder 2 and the raw material powder 3 may be produced by any production method.

[0299] For example, for the raw material powder 2 containing the M2 element source, it can be: manufactured by a method similar to the manufacturing method of the raw material powder 1 except that the M2 element source is used instead of the M1 element source; or manufactured by a manufacturing method of mixing a powder of zirconium oxide that does not contain a coloring component with at least any one of a compound and a salt containing the M2 element.

[0300] The raw material powder 2 containing a lanthanoid rare earth element can be produced by the same method as the raw material powder 1 except that a lanthanoid rare earth element source is used instead of the stabilizing element source and the M1 element source.

[0301] The source of the lanthanide rare earth element can be at least any one of the salts and compounds containing the lanthanide rare earth element, and can include one or more selected from the oxides, hydroxides, oxyhydroxides, halides, carbonates, sulfates, nitrates and acetates containing the lanthanide rare earth element, more preferably at least any one of the oxides, hydroxides and chlorides containing the lanthanide rare earth element, and further preferably an oxide containing the lanthanide rare earth element.

[0302] For example, the raw material powder 3 may be produced by the same method as the raw material powder 1 except that the M1 element source is not used.

[0303] [Pre-calcined body and method for producing the same]

[0304] The zirconium oxide composition of the present embodiment can be used as a precursor of a calcined body, and can be used in a method for producing a calcined body including a step of calcining the zirconium oxide composition of the present embodiment (hereinafter also referred to as a “calcining step”).

[0305] By calcining the zirconium oxide composition, a calcined body (hereinafter also referred to as “calcined body of the present embodiment”) can be obtained.

[0306] The calcination in the calcination step may be a heat treatment at a temperature lower than the sintering temperature of zirconium oxide, and is preferably sintered at normal pressure. The calcination method is any method that can obtain a calcined body having desired characteristics, and the following methods and conditions can be exemplified.

[0307] Pre-firing atmosphere: atmosphere other than reducing atmosphere, preferably oxidizing atmosphere,

[0308] More preferably, the atmosphere

[0309] Pre-burning temperature: above 800℃, above 900℃ or above 950℃, and

[0310] 1200℃ or less, 1150℃ or less or 1100℃ or less

[0311] Heating rate: 10℃ / hour or more or 30℃ / hour or more, and

[0312] 200℃ / hour or less or 150℃ / hour or less

[0313] The holding time at the calcination temperature (hereinafter also referred to as "calcination time") can be appropriately adjusted according to the shape, size and amount of the zirconium oxide composition to be calcined, and the type and performance of the calcination furnace. The calcination time can be 0.5 hours or more or 1 hour or more, and can be 7 hours or less or 3 hours or less.

[0314] When the zirconium oxide composition of the present embodiment contains a binder, it can be removed during the temperature rise to the calcination temperature. On the other hand, a step of removing the binder, i.e., a so-called degreasing step, may be provided before the calcination step. The method of removing the binder is arbitrary and can be appropriately adjusted according to the shape and size of the zirconium oxide composition, and the method and characteristics of degreasing. For example, heat treatment in an air atmosphere at 400°C or higher and lower than 800°C can be used.

[0315] The calcined body of the present embodiment is different from the powder and the molded body (powder compact), and is composed of fused particles. The fused particles have a structure at the initial stage of sintering, and the calcined body has a structure in which the particles are necked while maintaining a part of the shape of the powder particles contained in the zirconium oxide composition of the present embodiment. As a result, the calcined body has mechanical properties suitable for machining.

[0316] The shape of the calcined body of this embodiment may be any shape according to the purpose, etc. Examples of the shape of the calcined body include one or more selected from the group consisting of disk, column, cube, cuboid, polyhedron, sphere, and substantially spherical, and a dental restoration shape.

[0317] The measured density of the calcined body of the present embodiment (calcined body density) is 2.8 g / cm 3 Above or 3.2g / cm 3 In addition, 3.5 g / cm 3 Below or 3.4g / cm 3 Below, preferably 2.8 g / cm 3 Above and 3.5g / cm 3 Below, or 3.2gcm 3 Above and 3.4g / cm 3 It should be noted that since the calcined body is hardly densified, the density of the calcined body may be equal to the measured density of the molded body (molded body density).

[0318] The calcined body of the present embodiment only needs to have a hardness suitable for machining by CAD / CAM, and for example, a Vickers hardness of 25 HV or more and 150 HV or less (25 kgf / mm 2 Above and 150kgf / mm 2 The Vickers hardness of the calcined body of the present embodiment is preferably 30 HV or more, 40 HV or more, or 45 HV or more, and is preferably 70 HV or less, 60 HV or less, 55 HV or less, or 50 HV or less.

[0319] It is preferred that the variation in Vickers hardness between calcined bodies produced under the same conditions and having the same composition as the zirconium oxide composition of the present embodiment is small, and the standard deviation of the Vickers hardness between the calcined bodies is preferably 4 HV or less or 3 HV or less. The standard deviation of the Vickers hardness is preferably small, but may be 0 HV or more or more than 0 HV.

[0320] Furthermore, the calcined body of the present embodiment preferably has a small difference in hardness caused by a composition difference. For example, the absolute value of the difference in hardness of the calcined body obtained from the zirconium oxide composition of the present embodiment under the following molding conditions and calcining conditions relative to the calcined body obtained from a commercially available powder (product name: Zpex4, manufactured by Tosoh Corporation) under the same molding conditions and calcining conditions (hereinafter also referred to as "hardness difference") is preferably 10HV or less, 9HV or less, 7HV or less, 6HV or less, or 5HV or less. The smaller the hardness difference, the more preferred, but examples include 0HV or more, more than 0HV, 1HV or more, or 2HV or more. The hardness difference of the calcined body of the present embodiment can be exemplified as 0HV or more and 10HV or less, more than 0HV and less than 9HV, or 2HV or more and less than 5HV.

[0321] (Molding conditions) Molding method: Uniaxial pressurization and CIP treatment Uniaxial pressurization pressure: 49±3MPa

[0322] CIP pressure: 196±5MPa

[0323] (Pre-firing conditions) Pre-firing method: atmospheric pressure sintering

[0324] Atmosphere: atmospheric atmosphere

[0325] Firing temperature: 1000℃

[0326] Firing time: 1 hour

[0327] Heating rate: 50±5℃ / hour

[0328] Cooling speed: 300±10℃ / hour

[0329] The calcined body of the present embodiment can be used for known purposes, and one example of the calcined body is use as a calcined body for dental restorations, and another example of the calcined body is use as a dental mill blank.

[0330] [Sintered body and method for producing the same]

[0331] At least one of the zirconium oxide composition and the calcined body of the present embodiment can be used as a precursor of a sintered body. In addition, at least one of the zirconium oxide composition and the calcined body of the present embodiment can be used in a method for producing a sintered body having a step of sintering at least one of the zirconium oxide composition and the calcined body of the present embodiment (hereinafter also referred to as a "sintering step").

[0332] By sintering at least one of the zirconium oxide composition and the calcined body, a sintered body (hereinafter also referred to as “sintered body of the present embodiment”) can be obtained.

[0333] The sintering method in the sintering step can be any sintering method that densifies zirconium oxide. As the sintering method, it is preferred to use one or more sintering methods selected from pressure sintering, vacuum sintering and normal pressure sintering, more preferably normal pressure sintering, and further preferably normal pressure sintering under an atmospheric atmosphere. By normal pressure sintering, a sintered body can be obtained in the form of a normal pressure sintered body.

[0334] Preferred conditions for normal pressure sintering include the following.

[0335] Sintering atmosphere: atmosphere other than reducing atmosphere, preferably oxidizing atmosphere,

[0336] More preferably, the atmosphere

[0337] Processing temperature: more than 1200℃, more than 1300℃ or more than 1400℃, and

[0338] Below 1600℃, below 1550℃ or below 1500℃

[0339] Heating rate: 50℃ / hour or more, 100℃ / hour or more, or 150℃ / hour or more, and

[0340] 800℃ / hour or less or 700℃ / hour or less

[0341] The holding time at the treatment temperature (hereinafter also referred to as "sintering time") can be appropriately adjusted according to the shape, size and amount of the zirconium oxide composition to be sintered, and the type and performance of the sintering furnace. The sintering time can be 0.5 hours or more or 1 hour or less, and 5 hours or less or 3 hours or less.

[0342] Other preferred sintering conditions include the following conditions.

[0343] Sintering atmosphere: atmosphere other than reducing atmosphere, preferably oxidizing atmosphere,

[0344] More preferably, the atmosphere

[0345] Processing temperature: more than 1200℃, more than 1300℃ or more than 1400℃, and

[0346] Below 1600℃, below 1550℃ or below 1500℃

[0347] Heating rate: 30℃ / min or more or 50℃ / min or more, and

[0348] 300℃ / min or less or 250℃ / min or less

[0349] Sintering time: more than 1 minute or more than 5 minutes, and

[0350] Less than 1 hour or less than 0.5 hour

[0351] The sintered body of the present embodiment may have the same composition as the above-mentioned zirconium oxide composition and calcined body.

[0352] The sintered body of the present embodiment preferably has the same color tone as any color tone of the dental color tone sample. As the color tone of the sintered body of the present embodiment, it is more preferable to have a color tone of A1, A2, A3, A3.5, A4, B1, B2, B3, B4, C1, C2, C3, C4, D2, D3 or D4 of the dental color tone sample (for example, VITA classical shade guide).

[0353] The color tone of the sintered body varies according to its light transmittance. * a * b * When the color system represents the color tone of the dental color tone sample in the sintered body having a total light transmittance of 24 to 44%, the following color tones can be exemplified.

[0354] [Table 1]

[0355]

[0356] The sintered body of the present embodiment preferably has strength suitable for use as a dental restoration, and the three-point bending strength is preferably 550 MPa or more, 600 MPa or more, or 800 MPa or more. The three-point bending strength can be exemplified as less than 1200 MPa, less than 1100 MPa, or less than 1000 MPa, preferably 550 MPa or more and less than 1200 MPa, or 800 MPa or more and 1000 MPa or less.

[0357] The sintered body of this embodiment only needs to have light transmittance that can impart aesthetics equivalent to that of natural teeth. Such total light transmittance may be 10% or more, 15% or more, or 25% or more, or 40% or less, 35% or less, or 30% or less, preferably 10% or more and 40% or less, 15% or more and 35% or less, or 25% or more and 30% or less.

[0358] Furthermore, the sintered body of the present embodiment preferably has a small difference in total transmittance caused by composition difference. For example, it can be cited that the total transmittance of the sintered body obtained from the zirconium oxide composition of the present embodiment under the following molding conditions, pre-firing conditions and sintering conditions relative to the total transmittance of the sintered body obtained from the commercially available powder (product name: Zpex4, manufactured by Tosoh Corporation) under the same molding conditions, pre-firing conditions and sintering conditions (hereinafter also referred to as "transmittance ratio") is 0.5 or more, 0.6 or more, or 0.7 or more. The smaller the transmittance ratio, the better, but there is a tendency that the transmittance ratio of the sintered body with a darker color tone is larger. Therefore, the transmittance ratio can be exemplified as less than 1.0 or less than 0.9, preferably more than 0.5 and less than 1.0, or more than 0.7 and less than 0.9.

[0359] (Molding conditions) Molding method: Uniaxial pressing and CIP treatment

[0360] Uniaxial pressing pressure: 49±3MPa

[0361] CIP pressure: 196±5MPa

[0362] (Pre-firing conditions) Pre-firing method: atmospheric pressure sintering

[0363] Atmosphere: atmospheric atmosphere

[0364] Firing temperature: 1000℃

[0365] Firing time: 1 hour

[0366] Heating rate: 50±5℃ / hour

[0367] Cooling speed: 300±10℃ / hour

[0368] (Sintering conditions) Sintering method: atmospheric pressure sintering

[0369] Atmosphere: atmospheric atmosphere

[0370] Processing temperature: 1450℃

[0371] Sintering time: 2 hours

[0372] Heating rate: 600±20℃ / hour

[0373] Cooling speed: 600±50℃ / hour

[0374] The sintered body of this embodiment can be applied to known uses of zirconia, for example, as a structural material, an optical material, a dental material, a decorative material, and an exterior member of an electronic device, and is preferably used as a dental material, and more preferably as a dental restoration.

[0375] Above, the embodiments of the present invention have been described, but the present invention is not subject to any limitation of the above embodiments. For example, the mode of arbitrarily combining the constituent elements specifically described in the above embodiments, and the numerical range of arbitrarily combining the upper limit and the lower limit are also included in the present invention. In addition, the value obtained by replacing the upper limit and / or the lower limit with the value of the embodiment described below is also included in the present invention.

[0376] Example

[0377] Hereinafter, the present embodiment will be described in detail by way of examples, but the present embodiment is not limited to these examples.

[0378] (Composition Analysis)

[0379] The composition of the composition was measured by ICP analysis. As a pretreatment for the analysis, the sample powder was heat-treated at 1000° C. for 1 hour in an air atmosphere.

[0380] (BET specific surface area)

[0381] The BET specific surface area was measured using an automatic specific surface area measuring apparatus (apparatus name: TriStarII 3020, manufactured by Shimadzu Corporation) in accordance with JIS R 1626 by a BET multipoint method (5 points) under the following conditions.

[0382] Adsorption medium: N2

[0383] Adsorption temperature: -196℃

[0384] Pretreatment conditions: Degassing treatment at 250°C for more than 1 hour in an air atmosphere

[0385] (Crystal phase, tetragonal + cubic ratio)

[0386] The crystal phase was identified by XRD measurement under the following conditions using an X-ray diffractometer (apparatus name: Ultima IV, manufactured by RIGAKU Corporation).

[0387] Radiation source: CuKα radiation (λ = 0.15418nm)

[0388] Measurement mode: continuous scan

[0389] Scanning speed: 2° / min

[0390] Measuring range: 2θ = 26° to 33°

[0391] 2θ=72°~76°

[0392] Accelerating voltage and current: 40mA and 40kV

[0393] Divergence longitudinal limiting slit: 10mm

[0394] Divergence / entrance slit: 1°

[0395] Light receiving slit: open

[0396] Detector: Semiconductor detector (D / teX Ultra)

[0397] Filter: Ni filter

[0398] Goniometer radius: 185mm

[0399] The crystal phase can be identified by smoothing and background removal using an analysis program attached to an X-ray diffractometer (program name: comprehensive powder X-ray analysis software PDXL Ver.2.2, manufactured by RIGAKU), and contour fitting of the processed XRD pattern using a separate pseudo-Voigt function.

[0400] The tetragonal + cubic crystal ratio (T+C phase ratio) can be determined from the XRD patterns of the surfaces of the powder composition, calcined body, and sintered body according to the present embodiment using the above-mentioned formula.

[0401] (Average particle diameter)

[0402] The average particle diameter is measured by particle size distribution measurement using a Microtrac particle size distribution analyzer (device name: MT3100II, manufactured by Microtrac BEL) by a laser diffraction / scattering method. The measurement conditions are as follows.

[0403] Light source: semiconductor laser (wavelength: 780nm)

[0404] Voltage: 3mW

[0405] Refractive index of zirconium oxide: 2.17

[0406] Calculation mode: MT3000

[0407] The measurement sample was not subjected to dispersion treatment such as ultrasonic treatment, and the particle powder in a slowly agglomerated state was used as it is.

[0408] (Measured density)

[0409] The mass of the molded body and the calcined body was measured with a balance, and the volume was measured with a vernier caliper and the measured density was calculated from the dimensions. The measured density was calculated from the obtained mass and volume, and the density of the molded body was the density of the molded body and the density of the calcined body was the density of the calcined body.

[0410] (Vickers hardness)

[0411] Vickers hardness is measured using a Vickers hardness tester (device name: Q30A, manufactured by Qness). Under the following conditions, the indenter is statically pressed into the surface of the test sample, and the diagonal length of the indentation formed on the surface of the test sample is measured. The obtained diagonal length is used to calculate the Vickers hardness using the above formula.

[0412] Test sample: disc-shaped with a thickness of 3.0±0.5mm

[0413] Measuring load: 1kgf

[0414] Load holding time: 5 seconds

[0415] The measurement was performed on 10 points of the molded or calcined body produced under the same conditions, and the average value was used as the Vickers hardness. In addition, before the measurement, as a pretreatment, the measurement surface of the measurement sample was polished with #800 water-resistant abrasive paper to remove the unevenness exceeding 0.1 mm.

[0416] (Total light transmittance)

[0417] The total light transmittance was measured using a haze meter (device name: NDH4000, manufactured by Nippon Denshoku Co., Ltd.) and a D65 light source in accordance with JIS K7361-1. The measurement sample used was a disc-shaped sintered body having a thickness of 1.0±0.1 mm and double-sided polished to a surface roughness of Ra≤0.02 μm.

[0418] (tone)

[0419] The color tone was measured using a spectrophotometer (device name: CM-700d, manufactured by Konica Minolta) equipped with an illumination and light receiving optical system in accordance with geometric condition c of JIS Z 8722. The measurement conditions were as follows.

[0420] Light source: D65 light source

[0421] Viewing angle: 10°

[0422] Measurement method: SCI

[0423] As a test sample, cut out any part of the sintered body in the horizontal direction, and then mirror-polish the two sides of the sample to make the diameter 20mm×thickness 1.0±0.1mm and the surface roughness (Ra) less than 0.02μm. The test sample is placed on a white plate, and the two polished surfaces are used as evaluation surfaces. The color tone (L * 、a * and b * ) (Measurement with white background). The effective area for color tone evaluation is 10 mm in diameter.

[0424] (Three-point bending strength)

[0425] The three-point bending strength was measured by a method in accordance with JIS R 1601. The test specimen was a columnar shape with a width of 4 mm, a thickness of 3 mm, and a length of 45 mm. The measurement was performed by setting the distance between the fulcrums to 30 mm and applying a load in the horizontal direction of the test specimen.

[0426] <Synthesis of Raw Material Powder>

[0427] Synthesis example 1

[0428] Powders 1 to 9 were synthesized by the following method. That is, a hydrated zirconium oxide aqueous solution obtained by hydrolyzing a zirconium oxychloride aqueous solution, an iron (III) chloride aqueous solution having a FeCl3 concentration of 45% by mass, and yttrium chloride were mixed in a manner to form the composition of the powders in the following table, and raw material solutions were obtained respectively. The raw material solutions were dried in an air circulation atmosphere at 180°C to obtain dry powders, and then heat-treated in an air atmosphere at the temperature shown in the following table to obtain each pre-calcined powder. After mixing 199.9 g of the obtained pre-calcined powder and pure water with a ball mill, an acrylic resin and at least one of a slurry containing α-alumina powder and a slurry containing titanium oxide powder as required were added to prepare each slurry. The slurry was spray-dried in an air atmosphere at 180°C to obtain 9 kinds of granular powders (powders 1 to 9).

[0429] Synthesis example 2

[0430] A raw material solution was obtained in the same manner as in Synthesis Example 1 except that an aqueous solution of iron (III) chloride was not used, so as to have the composition of the powder shown in the table below. The raw material solution was dried in an air circulation atmosphere at 180° C. to obtain a dry powder, and then heat-treated in an air atmosphere at 1175° C. to obtain a calcined powder.

[0431] 199.9 g of the calcined powder, 0.1 g of α-alumina powder, 0.45 g of iron oxyhydroxide (FeOOH) powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain a granular powder (powder 10).

[0432] The results of Synthesis Examples 1 and 2 are shown in the following table.

[0433] [Table 2]

[0434]

[0435] Powders 1 and 10 both contain iron, but Powder 1 has a high strength ratio of 0.05%, a coarse strength ratio of 0%, a maximum strength ratio of 0.107, and a minimum value of the X-ray intensity ratio of 0. In contrast, Powder 10 has a high strength ratio of 2.04%, a coarse strength ratio of 0.54%, a maximum strength ratio of 0.901, and a minimum strength ratio of 0.

[0436] Synthesis example 3

[0437] A raw material solution was obtained in the same manner as in Synthesis Example 1 except that nickel oxide (NiO) powder was used instead of the iron (III) chloride aqueous solution, so as to have the composition of the powder shown in the table below. The raw material solution was dried at 180° C. in an air circulation atmosphere to obtain a dry powder, and then heat-treated at 1140° C. in an air atmosphere to obtain a calcined powder.

[0438] 199.9 g of the calcined powder, 0.1 g of α-alumina powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain a granular powder (powder 11).

[0439] Synthesis example 4

[0440] Without using nickel oxide (NiO powder), a raw material solution was obtained in the same manner as in Synthesis Example 1 so as to have the composition of the powder shown in the table below. The raw material solution was dried in an air circulation atmosphere at 180°C to obtain a dry powder, and then heat-treated in an air atmosphere at 1140°C to obtain a calcined powder.

[0441] 199.9 g of the calcined powder, 0.1 g of α-alumina powder, 0.1 g of nickel oxide powder and pure water were mixed in a ball mill, and acrylic resin was added to prepare slurry. The slurry was spray-dried in air at 180° C. to obtain a granular powder (powder 12).

[0442] The results of Synthesis Examples 3 and 4 are shown in the following table.

[0443] [Table 3]

[0444]

[0445] Synthesis example 5

[0446] Cobaltous oxide (Co3O4) powder was used instead of the aqueous solution of iron (III) chloride. In addition, the same method as in Synthesis Example 1 was used to obtain a raw material solution in a manner to obtain a powder composition as shown in the table below. The raw material solution was dried in an air circulation atmosphere at 180°C to obtain a dry powder, and then heat-treated in an air atmosphere at 1140°C to obtain a calcined powder.

[0447] 199.9 g of the calcined powder, 0.1 g of α-alumina powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain a granular powder (powder 13).

[0448] Synthesis example 6

[0449] Each raw material solution was obtained in the same manner as in Synthesis Example 1 except that the iron (III) chloride aqueous solution was not used, so as to have the composition of the powders shown in the table below. The raw material solutions were dried in an air circulation atmosphere at 180° C. to obtain dry powders, and then heat-treated in an air atmosphere at the calcination temperatures shown in the table below to obtain calcined powders.

[0450] 199.9 g of the calcined powder, 0.1 g of α-alumina powder, 0.1 g of cobalt oxide powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain granular powders (powders 14 and 15).

[0451] Separately, a granular powder (powder 16) was obtained in the same manner except that 199.9 g of the calcined powder, 0.1 g of α-alumina powder, 0.08 g of cobalt oxide powder, 0.4 g of titanium oxide powder, and pure water were mixed using a ball mill.

[0452] The results of Synthesis Examples 5 and 6 are shown in the following table.

[0453] [Table 4]

[0454]

[0455] Synthesis Example 7

[0456] In place of the aqueous solution of iron (III) chloride, manganese tetraoxide (Mn3O4) powder was used. In addition, a raw material solution was obtained in the same manner as in Synthesis Example 1 so as to have the composition of the powder shown in the table below. The raw material solution was dried in an air circulation atmosphere at 180°C to obtain a dry powder, and then heat-treated in an air atmosphere at 1140°C to obtain a calcined powder.

[0457] 199.9 g of the calcined powder, 0.1 g of α-alumina powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain a granular powder (Powder 17).

[0458] Synthesis example 8

[0459] A raw material solution having the composition of the powder shown in the table below was obtained by the same method as in Synthesis Example 1 except that the trimanganese tetraoxide powder was not used. The raw material solution was dried at 180° C. in an air circulation atmosphere to obtain a dry powder, and then heat-treated at 1175° C. in an air atmosphere to obtain a calcined powder.

[0460] 199.9 g of the calcined powder, 0.1 g of α-alumina powder, 0.1 g of trimanganese tetraoxide powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare slurry. The slurry was spray-dried in air at 180° C. to obtain a granular powder (powder 18).

[0461] The results of Synthesis Examples 7 and 8 are shown in the following table.

[0462] [Table 5]

[0463]

[0464] Synthesis example 9

[0465] Except that an aqueous solution of iron (III) chloride was not used and erbium oxide was used instead of yttrium chloride, the same method as in Synthesis Example 1 was used to obtain raw material solutions in a manner to have the composition of the powders shown in the table below. The raw material solutions were dried in an air circulation atmosphere at 180° C. to obtain dry powders, and then heat-treated in an air atmosphere at the calcination temperature shown in the table below to obtain calcined powders.

[0466] 199.9 g of the obtained calcined powder, 0.1 g of α-alumina powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain granular powders (powders 19 and 20). The results are shown in the table below.

[0467] [Table 6]

[0468]

[0469] Synthesis example 10

[0470] Except that no aqueous solution of iron (III) chloride was used, raw material solutions were obtained in the same manner as in Synthesis Example 1 so as to have the composition of the powders shown in the table below. The raw material solutions were dried in an air circulation atmosphere at 180° C. to obtain dry powders, and then heat-treated in an air atmosphere at the calcination temperature shown in the table below to obtain calcined powders.

[0471] 199.9 g of the calcined powder, 0.1 g of α-alumina powder and pure water were mixed in a ball mill, and then acrylic resin was added to prepare a slurry. The slurry was spray-dried in an air atmosphere at 180° C. to obtain granular powders (powders 21 and 23).

[0472] In addition, commercially available zirconium oxide powder (product name: Zpex4, manufactured by Tosoh Corporation) was used as the powder 22 .

[0473] The composition and physical properties of the granular powder are shown in the table below.

[0474] [Table 7]

[0475]

[0476] Examples 1 to 7 and Comparative Examples 1 to 3

[0477] Each powder was filled into a 200 mL polypropylene container at the mass ratio shown in the table below, and the container was stirred to dry mix the powders to obtain powder compositions of each example and comparative example. The results are shown in the table below.

[0478] [Table 8]

[0479]

[0480] Examples 1 and 4 and Comparative Example 1 are powders of a composition corresponding to a sintered body having a color tone of dental color tone sample C1. Examples 2 and 5 and Comparative Example 2 are powders of a composition corresponding to a sintered body having a color tone of dental color tone sample C3. Examples 3 and 6 and Comparative Example 3 are powders of a composition corresponding to a sintered body having a color tone of dental color tone sample C4.

[0481] Regarding the high strength ratio, Example 1 is 0% (0.002%), Example 2 is 0.02%, and Example 3 is 0.03%. It can be confirmed that the high strength ratio tends to increase with the increase in the amount of Fe2O3. On the other hand, the high strength ratio of Comparative Example 3 is 3.06%, which is more than 100 times that of Example 3. It should be noted that regarding the coarse strength ratio, Examples 1 to 3 are all 0%, while Comparative Example 3 is 0.38%, which can be confirmed that the iron of Comparative Example 3 is further condensed compared with the Examples.

[0482] The maximum intensity ratio was 0.053 for Example 1, 0.054 for Example 2, 0.057 for Example 3, and 0.334 for Comparative Example 3, and the minimum intensity ratio was 0.001 for Example 1, 0 for Example 2, 0 for Example 3, and 0.002 for Comparative Example 3. It was thus confirmed that, with respect to the intensity ratio range, Example 1 was 0.052, Example 2 was 0.054, and Example 3 was 0.057, whereas Comparative Example 3 was 0.332, and the Comparative Examples contained iron (M1 element) in a variety of condensed states compared to the Examples.

[0483] 3.0 g of the obtained powder was filled into a mold with a diameter of 25 mm, and uniaxial compression molding was performed at a pressure of 49 MPa, and then CIP treatment was performed at a pressure of 196 MPa to obtain a disk-shaped molded body (powder compact). These molded bodies were pre-calcined under the following conditions to obtain the pre-calcined bodies of each embodiment and comparative example.

[0484] Pre-burning temperature: 1000℃

[0485] Burn-in time: 1 hour

[0486] Heating rate: 50℃ / hour

[0487] Pre-burning atmosphere: atmospheric atmosphere

[0488] Cooling speed: 300℃ / hour

[0489] The calcined bodies of Examples 1 and 4 and Comparative Example 1 were designated as C1 calcined bodies, the calcined bodies of Examples 2 and 5 and Comparative Example 2 were designated as C3 calcined bodies, and the calcined bodies of Examples 3 and 6 and Comparative Example 3 were designated as C4 calcined bodies. The results are shown in the table below. It should be noted that the composition in the table below indicates the content of elements other than zirconium oxide (in terms of oxide).

[0490] [Table 9]

[0491]

[0492] It was confirmed that the molded body of the example had a Vickers hardness of 11.5 HV or more, and was less likely to have defects, although the density was about the same as that of the comparative example.

[0493] Measurement Example 1

[0494] The Vickers hardness of the calcined bodies of the examples and comparative examples was measured. The results are shown in the table below. It should be noted that the Vickers hardness was measured on 10 points of the calcined bodies obtained by repeatedly performing the operations of each example and comparative example. In addition, a calcined body was prepared by the same method as in the example except that powder 10 was used, and the difference in Vickers hardness (46.3 HV) from the obtained calcined body (hereinafter also referred to as "reference calcined body") was expressed as the hardness difference.

[0495] [Table 10]

[0496]

[0497] It can be confirmed that the calcined bodies of the examples and comparative examples have a tendency that the darker the color tone, the higher the Vickers hardness and the larger the standard deviation, from the C1 calcined body to the C4 calcined body. In addition, it can be confirmed that the calcined bodies of the examples have lower Vickers hardness and smaller standard deviation than the calcined bodies of the comparative examples in any color tone, and the variation in hardness between production batches is suppressed.

[0498] Among the C1 to C4 calcined bodies, the Vickers hardness of the calcined bodies of Examples was 47.3 HV to 50.8 HV, with a hardness difference of 5 HV or less, whereas the Vickers hardness of the calcined bodies of Comparative Examples was 53.4 HV to 65.8 HV, with a hardness difference of more than 10 HV.

[0499] Furthermore, the hardness difference between the calcined body obtained from the commercially available zirconium oxide powder is 5 HV or less, i.e., 1.0 HV to 4.5 HV, in the Examples, whereas it is 7 HV or more, i.e., 7.1 HV to 19.5 HV, in the Comparative Examples, which is a large hardness difference, and it can be confirmed that the difference increases as the color tone becomes darker.

[0500] <Production of Sintered Body>

[0501] The calcined bodies of the respective examples and comparative examples and the reference calcined body were sintered under the following conditions to obtain sintered bodies.

[0502] Sintering method: atmospheric pressure sintering

[0503] Sintering temperature: 1500℃

[0504] Sintering time: 2 hours

[0505] Heating rate: 600℃ / hour

[0506] Sintering atmosphere: atmospheric atmosphere

[0507] The obtained sintered bodies were designated as C1 sintered bodies for Examples 1 and 4 and Comparative Example 1, C3 sintered bodies for Examples 2 and 5 and Comparative Example 2, and C4 sintered bodies for Examples 3 and 6 and Sintering Example 3. In addition, the sintered bodies obtained from the reference calcined bodies were designated as reference sintered bodies. The results are shown in the table below. In the table below, the transmittance ratio indicates the total transmittance of each sintered body relative to the total transmittance (42%) of the reference sintered body.

[0508] [Table 11]

[0509]

[0510] The transmittance ratio and color tone of the sintered bodies of the examples and comparative examples are similar. This confirms that a sintered body having the same color tone and total light transmittance as a conventional sintered body can be obtained from the calcined body of the examples.

[0511] Embodiments 7 to 12

[0512] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0513] The obtained powder composition was molded and calcined in the same manner as in Example 1 to obtain calcined bodies of Examples 7 to 12. The results of the powder composition are shown in Table 12, and the results of the molded body and the calcined body are shown in Table 13.

[0514] It should be noted that the compositions in Table 13 indicate the contents other than zirconium oxide.

[0515] [Table 12]

[0516]

[0517] The high strength ratio is 0.01% (0.005%) in Example 7, 0.01% (0.011%) in Example 8, 0.01% (0.014%) in Example 9, 0.03% in Example 10, and 0.06% in Example 11. It can be confirmed that the high strength ratio tends to increase with the increase in the amount of Fe2O3. In addition, the coarse strength ratio is 0% in Examples 7 to 11.

[0518] The maximum strength ratio is 0.012 in Example 7, 0.015 in Example 8, 0.015 in Example 9, 0.057 in Example 10, and 0.128 in Example 11. In addition, the minimum strength ratio is 0 in all Examples 7 to 11, and the strength ratio range is 0.012 in Example 7, 0.015 in Example 8, and 0.015 in Example 9. As the amount of the stabilizing element increases, there is a tendency that the high strength ratio increases and the strength ratio range becomes wider.

[0519] [Table 13]

[0520]

[0521] Measurement Example 2

[0522] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 14, and the evaluation results of the sintered body are shown in Table 15.

[0523] [Table 14]

[0524]

[0525] The calcined bodies of Examples 7 to 12 all showed Vickers hardnesses of the same level as those of the calcined bodies of Examples 1 to 6, and no effect of the content of the stabilizing element (yttrium) on the Vickers hardness was observed.

[0526] [Table 15]

[0527]

[0528] It was confirmed that the three-point bending strength decreased and the transmittance increased by increasing the content of the stabilizing element (yttrium).

[0529] Examples 13 and 14

[0530] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0531] The obtained powder composition was molded and calcined in the same manner as in Example 1 to obtain calcined bodies of Examples 13 and 14. The results of the powder composition are shown in Table 16, and the results of the molded body and the calcined body are shown in Table 17. It should be noted that the composition in Table 17 indicates the content other than zirconium oxide.

[0532] [Table 16]

[0533]

[0534] [Table 17]

[0535]

[0536] It was confirmed that although the iron contents of powders 5 and 6 were different from each other, powder compositions and molded bodies having the same physical properties could be obtained by changing the mixing ratio.

[0537] Measurement Example 3

[0538] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 18, and the evaluation results of the sintered body are shown in Table 19.

[0539] [Table 18]

[0540]

[0541] [Table 19]

[0542]

[0543] It was confirmed from Examples 13 and 14 that even when calcined bodies were formed from powder compositions having different mixing ratios, similar calcined bodies and sintered bodies could be obtained.

[0544] Embodiments 15 to 17

[0545] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0546] The obtained powder composition was molded and calcined in the same manner as in Example 1 to obtain calcined bodies of Examples 15 and 17. The results of the powder composition are shown in Table 20, and the results of the molded body and the calcined body are shown in Table 21. It should be noted that the composition in Table 21 indicates the content other than zirconium oxide.

[0547] [Table 20]

[0548]

[0549] It was confirmed that Powder 8 had a higher BET specific surface area than the other powders, and that the BET specific surface area of ​​the obtained powder composition increased by increasing the mixing ratio.

[0550] [Table 21]

[0551]

[0552] Measurement Example 4

[0553] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 22, and the evaluation results of the sintered body are shown in Table 23.

[0554] [Table 22]

[0555]

[0556] It was confirmed that the calcined bodies obtained in Examples 15 to 17 had higher Vickers hardnesses than those in Examples 10 to 12, but had smaller standard deviations.

[0557] [Table 23]

[0558]

[0559] From the comparison between Examples 10 to 12 and Examples 15 to 17, it was confirmed that a sintered body having the same color tone could be obtained regardless of the BET specific surface area of ​​the powder composition.

[0560] Embodiment 18

[0561] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0562] The obtained powder composition was molded and calcined in the same manner as in Example 1 to obtain a calcined body of Example 18. The results of the powder composition are shown in Table 24, and the results of the molded body and the calcined body are shown in Table 25. It should be noted that the composition in Table 25 represents the content of elements other than zirconium oxide (in terms of oxide).

[0563] [Table 24]

[0564]

[0565] In Example 18, the high strength ratio is 0.07%, the coarse strength ratio is 0%, the maximum strength ratio is 0.148, and the minimum strength ratio is 0.003. In addition, the strength ratio range is 0.145.

[0566] [Table 25]

[0567]

[0568] Measurement Example 5

[0569] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 26, and the evaluation results of the sintered body are shown in Table 27.

[0570] [Table 26]

[0571]

[0572] [Table 27]

[0573]

[0574] In Examples 12 and 18 in which the alumina content was 0.05 mass % or less, the calcined bodies had the same Vickers hardness regardless of the alumina content. In addition, the obtained sintered bodies had the same color tone, three-point bending strength, and transmittance.

[0575] Examples 19 to 24 and Comparative Examples 4 to 6

[0576] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0577] The obtained powder composition was molded and calcined in the same manner as in Example 1 to obtain calcined bodies of each Example and Comparative Example. The results of the powder composition are shown in Table 28, and the results of the molded body and calcined body are shown in Table 29. It should be noted that the composition in Table 29 represents the content of elements other than zirconium oxide (in terms of oxide).

[0578] [Table 28]

[0579]

[0580] The high strength ratio was 99.24% for Example 22 and 99.33% for Example 24. The coarse strength ratio was 5.64 for Example 22 and 6.66 for Example 24.

[0581] The maximum strength ratio was 0.127 in Example 22 and 0.140 in Example 24, and the minimum strength ratio was 0.036 in Example 22 and 0.032 in Example 24. It was thus confirmed that the strength ratio range was 0.091 in Example 22 and 0.108 in Example 24, and there was a tendency for the strength ratio range to be wider than when the M1 element was iron.

[0582] [Table 29]

[0583]

[0584] It was confirmed that the molded body of the example had a Vickers hardness of 11.0 HV or higher, which was higher than that of the comparative example, and was a molded body that was less likely to have defects.

[0585] Measurement Example 6

[0586] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 30, and the evaluation results of the sintered body are shown in Table 31.

[0587] [Table 30]

[0588]

[0589] Among the calcined bodies that gave sintered bodies with the same color tone, the calcined bodies of the examples had lower hardness than the calcined bodies of the comparative examples, and the hardness difference was small. In addition, it was confirmed that the standard deviation was small and the variation in hardness between batches was small.

[0590] [Table 31]

[0591]

[0592] It was confirmed that sintered bodies having the same color tone could be obtained from any of the calcined bodies in Examples and Comparative Examples.

[0593] Examples 25 to 30 and Comparative Examples 7 to 9

[0594] The respective powders were charged into a 200 mL polypropylene container at the mass ratios shown in the following table, and the container was stirred to dry mix them, thereby obtaining powder compositions of the respective Examples and Comparative Examples.

[0595] The obtained powder composition was molded and calcined by the same method as in Example 1 to obtain calcined bodies of each Example and Comparative Example. The results of the powder composition are shown in Table 32, and the results of the molded body and calcined body are shown in Table 33. It should be noted that the composition in Table 33 represents the content of elements other than zirconium oxide (in terms of oxide).

[0596] [Table 32]

[0597]

[0598] In Example 27, the high strength ratio is 99.42%, the coarse strength ratio is 4.51%, the maximum strength ratio is 0.125, and the minimum strength ratio is 0.033, and the strength ratio range is 0.092.

[0599] [Table 33]

[0600]

[0601] It was confirmed that the Vickers hardness of the molded bodies of the examples was higher than that of the comparative examples, 11.0 HV or more, and that the molded bodies were less likely to have defects.

[0602] Measurement Example 7

[0603] The Vickers hardness of the calcined body was measured, and a sintered body was prepared and evaluated by the same method as in Measurement Example 1. The Vickers hardness measurement results are shown in Table 34, and the evaluation results of the sintered body are shown in Table 35.

[0604] [Table 34]

[0605]

[0606] Among the calcined bodies that gave sintered bodies with the same color tone, the calcined bodies of the examples had lower hardness than the calcined bodies of the comparative examples, and the hardness difference was small. In addition, it was confirmed that the standard deviation was small and the variation in hardness between batches was small.

[0607] [Table 35]

[0608]

[0609] It was confirmed that sintered bodies having the same color tone could be obtained from any of the calcined bodies in Examples and Comparative Examples.

[0610] The entire contents of the specifications, claims, and abstracts of Japanese Patent Application No. 2022-149612 filed on September 20, 2022 and Japanese Patent Application No. 2023-038003 filed on March 10, 2023 are cited herein and introduced as a disclosure of the specification of the present invention.

Claims

1. A zirconium oxide composition, characterized in that Containing a first transition metal element, a coloring element, and zirconium oxide containing a stabilizing element, The first transition metal element is one or more selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd) and silver (Ag), The coloring element is at least one of a lanthanide rare earth element and a second transition metal element different in type from the first transition metal element. The content of the first transition metal element is 100 mass ppm or more, The content of the second transition metal element is less than 100 mass ppm, and The zirconium oxide composition satisfies at least any one of the following characteristics: When the characteristic X-ray of the zirconium element and the characteristic X-ray of the first transition metal element are measured, the proportion of the measurement points at which the ratio of the intensity of the characteristic X-ray of the first transition metal element to the intensity of the characteristic X-ray of the zirconium element is 0.05 or more is less than 3% of all the measurement points; and When the characteristic X-rays of zirconium and the characteristic X-rays of the first transition metal element are measured, the distribution width of the ratio of the intensity of the characteristic X-rays of the first transition metal element to the intensity of the characteristic X-rays of zirconium is less than 0.

3.

2. The zirconium oxide composition according to claim 1, wherein When the characteristic X-rays of zirconium and the characteristic X-rays of the first transition metal element are measured, the distribution width of the ratio of the intensity of the characteristic X-rays of the first transition metal element to the intensity of the characteristic X-rays of zirconium is less than 0.

3.

3. The zirconium oxide composition according to claim 1 or 2, wherein When measuring the characteristic X-rays of zirconium and the characteristic X-rays of the first transition metal element, the proportion of measurement points where the intensity ratio of the characteristic X-rays of the first transition metal element to the characteristic X-rays of zirconium is 0.05 or more is less than 3% of all measurement points.

4. The zirconium oxide composition according to any one of claims 1 to 3, wherein The second transition metal element is one or more transition metal elements selected from the group consisting of manganese, iron, cobalt, nickel, copper, molybdenum, technetium, ruthenium, rhodium, palladium and silver.

5. The zirconium oxide composition according to any one of claims 1 to 4, wherein The lanthanide rare earth element is one or more selected from praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), erbium (Er) and ytterbium (Yb).

6. The zirconium oxide composition according to any one of claims 1 to 5, wherein The lanthanide rare earth element is a lanthanide rare earth element solid-dissolved in zirconium oxide.

7. The zirconium oxide composition according to any one of claims 1 to 6, wherein The content of the lanthanoid rare earth element is 1.0 mass % or less.

8. The zirconium oxide composition according to any one of claims 1 to 7, wherein The zirconium oxide composition contains one or more third transition metal elements selected from the group consisting of titanium (Ti), vanadium (V) and niobium (Nb).

9. The zirconium oxide composition according to any one of claims 1 to 8, wherein The zirconium oxide composition includes at least one selected from the group consisting of aluminum oxide (Al2O3), silicon dioxide (SiO2) and germanium oxide (Ge2O3).

10. The zirconium oxide composition according to any one of claims 1 to 9, wherein The BET specific surface area of ​​the zirconium oxide composition is 8 m 2 / g or more and 15m 2 / g or less.

11. The zirconium oxide composition according to any one of claims 1 to 10, wherein The zirconium oxide composition is in the form of powder.

12. The zirconium oxide composition according to claim 11, wherein 3.0±0.1 g of the zirconium oxide composition was filled into a mold with a diameter of 25 mm, and subjected to uniaxial press molding at a pressure of 49 MPa. The measured density after CIP treatment at a pressure of 196 MPa was 3.2 g / cm 3 above.

13. The zirconium oxide composition according to any one of claims 1 to 10, wherein The zirconium oxide composition is a shaped body.

14. The zirconium oxide composition according to claim 13, wherein The zirconium oxide composition has a Vickers hardness of 11.0 or more.

15. A method for producing a calcined body, characterized in that: The method comprises the step of pre-calcining the zirconium oxide composition according to any one of claims 1 to 14.

16. A method for producing a sintered body, characterized in that: The method comprises the step of sintering the calcined body obtained by the production method according to claim 15.

Citation Information

Patent Citations

  • Preparing method of zirconia mill blank for dental cutting and machining using precipitate

    EP3892254A1

  • Manufacturing method of laser diode, and laser diode

    JP2022149612A

  • Spray concrete transportation carriage and construction method of spray concrete

    JP2023038003A

  • Colored translucent zirconia sintered body and its use

    US9428422B2